Composite polyelectrolyte-ceramic membrane

By adopting a double-layer polyelectrolyte membrane structure in a proton exchange membrane fuel cell, the perfluorosulfonic acid polymer and crystalline metal oxide layer are used to reduce hydrogen permeability and improve membrane stability, the fuel efficiency reduction and membrane damage caused by hydrogen permeability are solved, and higher fuel cell performance and service life are achieved.

CN119654721APending Publication Date: 2025-03-18CELADYNE TECH INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380056265.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-19
Filing Date
2023-06-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In existing proton exchange membrane fuel cells (PEMFCs), hydrogen permeation leads to a decrease in fuel efficiency, a decrease in cathode potential and free radical formation, which in turn damages membrane stability.

Method used

A bilayer polyelectrolyte membrane structure is adopted, in which the first layer consists of perfluorosulfonic acid (PFSA) polymer and the second layer contains crystalline metal oxides, such as cerium oxide, by coating techniques, to reduce hydrogen permeation and stabilize the membrane.

Benefits of technology

It effectively reduces hydrogen permeability, improves the durability and stability of the membrane, and extends the service life of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005256664810000091
    Figure BDA0005256664810000091
  • Figure BDA0005256664810000092
    Figure BDA0005256664810000092
  • Figure BDA0005256664810000093
    Figure BDA0005256664810000093
Patent Text Reader

Abstract

The present disclosure relates to a bilayer polyelectrolyte membrane comprising a first layer and a second layer wherein the first layer comprises a perfluorosulfonic acid and the second layer comprises a metal oxide, and wherein the first layer is disposed on the second layer. The present disclosure also relates to a method of manufacturing the bilayer polyelectrolyte membrane, and a membrane electrode assembly and a fuel cell comprising the bilayer polyelectrolyte membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 348,715, filed on June 3, 2022, and U.S. Provisional Application No. 63 / 433,573, filed on December 12, 2022. The entire teachings of each of the above applications are incorporated herein by reference.

[0003] Government support

[0004] This invention was made with government support under Grant No. DE-SC0021832 awarded by the Department of Energy and Grant No. DE-AR0001242 awarded by ARPA-E. The government has certain rights in this invention. Background Art

[0005] Proton exchange membrane based fuel cells (PEMFCs) are eco-friendly energy conversion devices that operate at low temperatures and are more efficient than existing internal combustion engines. With these advantages, PEMFCs have become a popular alternative to fossil fuels in the transportation industry and have the potential to be used in a wide range of applications such as portable devices and stationary power systems.

[0006] The proton exchange membrane (PEM), which conducts protons and serves to separate the cathode from the anode, is one of the most important components of a PEMFC. The PEM significantly affects the overall performance of the fuel cell; therefore, improving the efficiency of the fuel cell requires a PEM that has high ionic conductivity, has low fuel crossover, and provides high physicochemical and mechanical stability. Because PEMFC uses a thin film as its electrolyte, these devices are more portable and compact than other types of fuel cells. However, the membrane may also allow the permeation of fuel gas (hydrogen), which adversely affects the cell efficiency. In addition, due to the free radicals formed on the electrodes, such as OH, the PEM can also pass through the electrodes to form a large number of proton exchange membranes, which can affect the efficiency of the cell. · and OOH · Therefore, there is a need for a PEM with high ionic conductivity, reduced hydrogen permeation and stability to free radical oxidants. Summary of the invention

[0007] In a first embodiment, the present invention is a bilayer polyelectrolyte membrane comprising: a first layer disposed on a second layer, wherein: the first layer comprises a perfluorosulfonic acid (PFSA) polymer, and the second layer comprises a crystalline metal oxide.

[0008] In a second embodiment, the present invention is a method for manufacturing a double-layer polyelectrolyte membrane described herein with respect to the first embodiment and its various aspects, the method comprising: providing a first layer having a first side, and a suspension comprising a metal oxide and a solvent; and coating the first side of the first layer with the suspension to produce a coated first layer.

[0009] In a third embodiment, the present invention is a membrane electrode assembly (MEA) comprising: a double-layer polyelectrolyte membrane as described herein with respect to the first embodiment and its various aspects; a cathode; and an anode, wherein the double-layer electrolyte membrane is disposed between the anode and the cathode.

[0010] In a fourth embodiment, the invention is a fuel cell comprising one or more MEAs described herein with respect to the third embodiment and various aspects thereof and one or more gas flow bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Due to hydrogen permeation Schematic diagram of membrane degradation.

[0012] Figure 2 Schematic diagram showing reduced hydrogen permeation and thus reduced degradation of the PFSA layer due to the presence of a metal oxide-containing layer on the PFSA layer.

[0013] Figure 3 Graphs showing theoretically calculated values ​​of hydrogen permeation and the resistance of a PFSA membrane coated with a layer containing a metal oxide as a function of the thickness of the metal oxide layer are shown.

[0014] Figure 4 Shows 211 membrane and a composite layer coated with cerium oxide nanocrystals and 75% cross-linked polyethylene glycol diacrylate (PEG(DA)) Cyclic voltammogram of the 211-layer film.

[0015] Figure 5 A graph is shown which demonstrates 211 membrane (square) and a composite layer coated with cerium oxide nanocrystals and 75% cross-linked PEG (DA) Fuel cell polarization and power curves for a 211-layer membrane (diamonds).

[0016] Figure 6 A graph is shown which demonstrates Results of Faster Accelerated Stress Testing (FAST) of the 211 membrane and a membrane comprising a composite layer containing cerium oxide nanocrystals and 75% cross-linked PEG (DA).

[0017] Figure 7 A schematic diagram of a fuel cell containing a PEM is shown.

[0018] Figure 8 A graph is shown which demonstrates 211 membrane and a cerium oxide nanocrystal-crosslinked PEG (DA) layer Comparison of the relationship between coating thickness and H2 permeation measurements of 211 membranes with theoretically calculated values.

[0019] Fig. 9 Schematic diagram showing the radical scavenging mechanism of cerium oxide.

[0020] Fig.10 shows the sPPS 1 H NMR spectrum.

[0021] Fig.11 Shows 211 membrane and a composite layer coated with cerium oxide and cross-linked polyethylene glycol diacrylate (PEG(DA)) 211 layers of film (in Cyclic voltammogram of a 1 μm thick coating on 211 containing 35 vol% 4 nm CeO2 particles in cross-linked PEG(DA) (75% cross-linked).

[0022] Fig.12 A graph is shown which demonstrates 211 membrane (solid squares) and a membrane comprising a composite layer coated with cerium oxide and cross-linked PEG (DA) 211 layers of membrane (hollow square) (in Polarization and power curves of a fuel cell containing a 1 μm thick coating of 35 vol% 4 nm CeO2 particles in cross-linked PEG(DA) (75% cross-linked) on 211.

[0023] Fig.13 A graph is shown which demonstrates 211 membrane (squares) and membranes containing a composite layer containing cerium oxide and cross-linked PEG (DA) (diamonds) ( Results of Faster Accelerated Stress Testing (FAST) of a 1 μm thick coating on 211 containing 35 vol% 4 nm CeO2 particles in cross-linked PEG(DA) (75% cross-linked).

[0024] Fig.14 A graph is shown which shows a composite layer comprising a metal oxide and a cross-linked PEG (DA) coated with 211 layers of film (ZrO2 – circles; MnO2 – squares; TiO2 – diamonds, Nb2O3 – triangles; Fuel cell polarization and power curves for a 1 μm thick coating comprising 35 vol% 4 nm metal oxide particles in cross-linked PEG(DA) (75% cross-linked) on 211.

[0025] Fig.15 A graph is shown showing a composite layer comprising CeO2 and polyethyleneimine cross-linked with dibromopropane (squares) or polyphenylsulfone (PPS) cross-linked with DMSO (circles). 211 layers of film (in Polarization and power curves of a fuel cell containing a 1 μm thick coating of 35 vol% 4 nm CeO-2 particles in cross-linked polyethyleneimine (50% cross-linked) or PPS (50% cross-linked) on 211.

[0026] Fig.16 The 25 μm 211 membrane, a 1 μm thick coating comprising 35 vol% 4 nm CeO2 particles in cross-linked PEG (DA) (75% cross-linked), and a 25 μm membrane coated with a 1 μm thick coating comprising 35 vol% 4 nm CeO2 particles in cross-linked PEG (DA) (75% cross-linked). Area specific resistance value of the 211-layer double-layer film.

[0027] The foregoing will become apparent from the following more particular description of example embodiments of the invention, as illustrated in the accompanying drawings, in which like reference numerals refer to the same parts throughout the different views. The drawings are not necessarily drawn to scale, emphasis instead being placed upon illustrating embodiments of the invention. DETAILED DESCRIPTION

[0028] Following is a description of example embodiments of the invention.

[0029] Hydrogen permeation is the undesired diffusion of hydrogen from the anode through the membrane to the cathode in a fuel cell. Hydrogen permeation can have at least three effects, including reduced fuel efficiency, reduced cathode potential, and formation of aggressive peroxide radicals. The permeated hydrogen can react directly with oxygen at the cathode surface, resulting in a lower cathode potential than the cathode potential of the lower fuel cell. More seriously, this direct reaction between H2 and O2 at the cathode can produce peroxide radicals, which not only attack the catalyst layer, but also the membrane, resulting in significant catalyst layer and membrane degradation. In addition, it has been confirmed that hot spots or hydrogen peroxide formed by the highly exothermic chemical reaction between H2 and O2 can also cause pinholes in the membrane, thereby destroying the MEA and causing safety issues. This hydrogen permeation can also lead to accelerated sintering of the catalyst. The presence of accidental Cu and Fe will further catalyze the decomposition of H2O2 into reactive oxygen radicals. In order to address this root cause, the membrane can be made more durable by reducing the hydrogen permeability across the membrane. According to the Maxwell permeability model, ceramic additives can reduce gas permeability in polymer composites. Compared to the H2 permeability of hydrated Nafion (120 barrer), for the SiO2-polyethylene oxide (PEO) system with 35 vol% ceramic content, the H2 permeability is 8 barrer, while the polysulfone-PEO random copolymer has a H2 permeability of 2 barrer.

[0030] Lifespan has always been one of the core concerns of proton exchange membrane fuel cells, especially in commercial applications. Membrane failure caused by chemical degradation may lead to the collapse of the entire fuel cell system. Proton exchange membranes with enhanced chemical durability can be manufactured by adding free radical scavengers. Free radical scavengers are a series of compounds that can preferentially react with harmful free radicals rather than ionomers, so that the membrane is protected. In some embodiments, the present disclosure shows that crystalline metal oxides of reducible metals can be used as free radical scavengers (for the mechanism of free radical scavenging by cerium oxide, see Fig. 9 ), while acting as a proton conductor and reducing hydrogen permeation. The free radical scavenging capacity is determined by the concentration of the scavenging species. Taking cerium as a typical example, the free radical scavenger can be added as a cerium salt, crystalline cerium oxide nanoparticles, or amorphous cerium oxide particles. Particles are used instead of salts to limit the migration of cerium in the fuel cell in a hydrated environment. Crystalline nanoparticles are used instead of amorphous particles because the surface crystalline material can carry a higher concentration of active Ce 3+ The concentration of active species other than free cations in the case of metal oxides can be improved by reducing the nanoparticle size or introducing strain in the lattice.

[0031] Without wishing to be bound by any particular theory, it is believed that the interaction between the metal oxide and the polymer is limited to weak van der Waals interactions, because the surface of the crystalline metal oxide is usually covered by organic ligands after synthesis. In order to introduce stronger interactions, such as hydrogen bonds, covalent bonds and ionic interactions, metal oxides with exposed surfaces and active MO, MH and M-OH groups are preferred. On one side of the polymer, chains with chelating properties such as amines, carboxylates, phosphates and hydroxyls (for hydrogen bonding) are preferred. By introducing stronger interactions, higher crystalline metal oxide loadings can be achieved without causing macroscopic phase separation of particles to the free surface, which is beneficial for properties proportional to the volume fraction such as electrical conductivity and gas permeability.

[0032] Composites of crystalline metal oxide nanoparticles can exhibit both low and high gas permeabilities, depending on the pairing of the nanoparticles with the polymer. Previous studies of nanoparticles with weak interactions with the host polymer have shown that composites can exhibit significantly higher gas permeabilities in systems where the nanoparticle component is impermeable because the weak interactions result in an increase in the free volume of the polymer in the system. In other words, the weak interactions result in a disordered and gas-permeable interface between the nanoparticle and the polymer that can serve as a pathway for rapid gas transport in the system.

[0033] It has been previously shown that metal oxide / polymer complexes without the deliberate introduction of salts (typically alkali and alkaline earth metal salts) do not exhibit ion-conducting properties. This understanding has been extrapolated to the case of proton-conducting systems, such that metal oxides are typically added to polymers in the presence of an acid or base (either as a stand-alone salt, such as phosphoric acid, or anchored to the polymer backbone in the case of a polymeric acid). The present disclosure unexpectedly shows that metal oxide / polymer complexes can exhibit significant ionic conductivity at high humidity in the absence of salts, which may be attributed to the inherent concentration of protons and hydroxyl groups on the metal oxide surface.

[0034] In some embodiments, the present disclosure relates to a bilayer polyelectrolyte membrane that exhibits reduced hydrogen permeation and improved membrane durability. The membrane comprises perfluorosulfonic acid (PFSA) such as In some embodiments, the coating comprises a metal oxide, such as cerium oxide, distributed in a polymer matrix. The coating has lower hydrogen permeability than PFSA and reduces the level of peroxide radicals, thereby reducing hydrogen permeation through the membrane and improving membrane durability ( Figure 1 and 2 ).

[0035] Figure 3The graph in shows the design criteria for the coated membrane. The graph shows the theoretically calculated values ​​of H2 permeation and the resistance of the coated PFSA as a function of coating thickness. Figure 4 The cyclic voltammogram in 211 and coated with a 700 nm layer of cerium oxide nanocrystals distributed in 75% cross-linked PEG (DA) 211 Hydrogen permeation measurements. Figure 5 The graph in Figure 2 shows 211 and coated with a layer consisting of cerium oxide nanocrystals distributed in a 75% cross-linked PEG (DA) coating 211 fuel cell polarization and power curves. These data show that compared with the uncoated The coating reduces H2 penetration by 25% compared to 211. In addition, Figure 6 Results from the Faster Accelerated Stress Test (FAST) in the study showed that the presence of cerium oxide nanocrystals in the cross-linked PEG (DA) coating at least doubled the durability of the membrane. The membrane failure time of 211 was about 5000 equivalent hours, while for 1 μm cerium oxide nanocrystals in a cross-linked PEG (DA) coating 211, the time to failure was not reached within the standard test duration of 10,000 equivalent hours. Figure 8 The curve graph in shows that Cerium oxide nanocrystals in a cross-linked PEG (DA) coating on 211 tune H2 permeation over a range of coating thicknesses. The graph shows that hydrogen permeation can be tuned by varying the coating thickness and Reduction of hydrogen permeation by more than 50% has been achieved using various thicknesses of cerium oxide nanocrystal / cross-linked PEG (DA) coatings on 211.

[0036] Fig.14 The graph in FIG. 1 shows a composite layer comprising nanocrystalline ZrO2, MnO2, TiO2, Nb2O3 and cross-linked PEG (DA) coated with Fuel cell polarization and power curves for a 211-layer membrane. The data demonstrate that a variety of reducible metal oxide nanocrystals can be used in the bilayer composite membrane.

[0037] Fig.15 The graphs in FIG. 1 show fuel cell polarization and power curves for membranes, including graphs showing the results of a membrane comprising a composite layer coated with CeO2 and polyethyleneimine cross-linked with dibromopropane or polyphenylsulfone (PPS) cross-linked with DMSO. Plot of fuel cell polarization and power curves for a 211 layer membrane. The data demonstrate that a wide variety of cross-linked polymers can be used in a bilayer composite membrane.

[0038] definition

[0039] Numerical ranges include numbers that define the range. For example, "x is an integer between 5 and 14" means that x can be 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14. Taking into account significant figures and errors associated with measurement, measured values ​​and measurable values ​​should be understood as approximate values. As used in this application, the terms "about" and "approximately" have the meanings understood in the art; using one of them instead of the other does not necessarily mean a different range. Unless otherwise specified, the numbers used in this application, whether or not with modified terms such as "about" or "approximately", should be understood to cover normal deviations and / or fluctuations as understood by ordinary technicians in the relevant field. In certain embodiments, the term "about" or "approximately" refers to a series of values ​​falling in either direction of the stated reference value (greater than or less than the stated reference value) of 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% or less, unless otherwise specified or otherwise obvious from the context (except when such a number exceeds 100% of the possible value).

[0040] As used herein, the term "double-layer polyelectrolyte membrane" refers to a membrane containing two layers disposed on top of each other, each layer comprising a polyelectrolyte. The two layers may be adhered to each other by the formation of chemical bonds or by van der Waals interactions.

[0041] As used herein, "characteristic size" refers to a crystal size that can be measured, for example, by known methods used in the art (including, for example, microscopy), and for spherical crystals, the characteristic size is the diameter of the crystal. For non-spherical crystal morphology, the characteristic size of a single crystal can be any dimension selected from the length, width, and height of the crystal, which are randomly designated as X, Y, and Z, respectively, including the following options (X=Y=Z), (X≠Y≠Z), (X=Y, X≠Z), (X=Z, X≠Y), (X≠Z, Y=Z).

[0042] The term "crystal", "crystals" or "crystalline" refers to a substance whose constituent atoms, molecules or ions are arranged in a substantially uniform, repeating three-dimensional pattern. The pattern can be detected according to known methods used in the chemical arts, including, for example, visual identification of crystals and identification by X-ray diffraction (e.g., powder X-ray diffraction (PXRD) and single crystal X-ray diffraction (SXRD)).

[0043] As used herein, the term "metal oxide" refers to a compound comprising one or more metal cations and oxide anions. Examples of metal oxides include, but are not limited to, titanium oxide, zirconium oxide, hafnium oxide, vanadium oxide, niobium oxide, tantalum oxide, chromium oxide, molybdenum oxide, tungsten oxide, manganese oxide, iron oxide, cobalt oxide, nickel oxide, cerium oxide, gadolinium oxide, and samarium oxide as well as oxides of other d-block elements and f-block elements. As used herein, the term "metal oxide" does not include polyoxometalates. "Polyoxometalates" refers to a material comprising polyatomic ions (usually anions) consisting of three or more transition metal oxyanions linked together by shared oxygen atoms to form a closed three-dimensional framework. The metal atoms in the polyoxometalates are typically Group 6 (Mo, W) or Group 5 (V, Nb, Ta) transition metals in their high oxidation states.

[0044] As used herein, "reducible metal oxide" refers to a metal oxide that can have many different valence states (or oxidation states) (e.g., two or more of +1, +2, +3, +4, +5, etc.) either in bulk or as defect states on the surface of the metal oxide. For example, cerium oxide and titanium oxide are reducible oxides because both Ce and Ti can have oxidation states of +3 and +4.

[0045] As used herein, the term "dopant" is an element introduced in small amounts into a chemical material such as a metal oxide to alter its optical, electronic, photocatalytic and other properties. When doped into a crystalline substance, atoms of the dopant are incorporated into the crystal lattice of the substance. Dopants include, but are not limited to, elements such as Gd, Sm, Nb, Ce and Si.

[0046] As used herein, the term "degree of sulfonation" refers to the number of repeating units having at least one sulfonic acid / sulfonate group. For example, a 20% degree of sulfonation means that 20% of the repeating units of the polymer are sulfonated, while a 100% degree of sulfonation means that each repeating unit in the polymer contains one sulfonic acid / sulfonate group. This may include polymers containing multiple sulfonic acid / sulfonate groups (e.g., disulfonated, trisulfonated, tetrasulfonated, etc.) per repeating unit. In some embodiments, the sulfonated polymer may contain an average of 2 sulfonic acid groups per repeating unit, which corresponds to a 200% degree of sulfonation. In some embodiments, the sulfonated polymer may contain an average of 2, 3, 4, or 5 sulfonic acid groups per repeating unit, which corresponds to 200%, 300%, 400%, or 500% degrees of sulfonation, respectively. In some embodiments, the sulfonated polymer may contain an average of 1.5 to 2.5 sulfonic acid groups per repeating unit, which corresponds to a 150% to 200% degree of sulfonation.

[0047] The sulfonated polymers of the present disclosure can also be characterized by the average number of sulfonic acid groups per repeating unit. For example, sulfonated polyphenylsulfone (sPPS) can contain 1, 2, 3, 4, 5, 6, 7, or 8 sulfonic acid groups per repeating unit. For example, a repeating unit of sPPS can contain 2 sulfonic acid groups:

[0048]

[0049] Alternatively, the repeating unit of sPPS may contain 4 or 6 sulfonic acid groups:

[0050]

[0051] In a given polymer, some repeating units may have, for example, 1 sulfonic acid group, some repeating units may have 2 sulfonic acid groups, and some repeating units may have 3 or more sulfonic acid groups. 1 The number of sulfonic acid groups per repeating unit measured in the bulk polymer by H NMR spectroscopy or ion exchange capacity corresponds to the average number of sulfonic acid groups over all repeating units of the polymer.

[0052] As used herein, the term "polyphenylsulfone" refers to a polymer comprising the following repeating units:

[0053]

[0054] As used herein, the term "polyetheretherketone" refers to a polymer comprising the following repeating units:

[0055]

[0056] As used herein, the term "polyphosphazene" refers to a polymer comprising the following repeating units:

[0057]

[0058] As used herein, the term "polybenzimidazole" refers to a polymer comprising the following repeating units:

[0059]

[0060] As used herein, the term "polyethersulfone" refers to a polymer comprising the following repeating units:

[0061]

[0062] As used herein, the term "polyphenylene ether" refers to a polymer comprising the following repeating units:

[0063]

[0064] As used herein, the term "polyaryletherketone" refers to a polymer comprising one or more of the following repeating units:

[0065]

[0066]

[0067] As used herein, the term "polysulfone" refers to a polymer comprising the following repeating units:

[0068]

[0069] As used herein, the term "polysulfide sulfone" refers to a polymer comprising the following repeating units:

[0070]

[0071] As used herein, the term "polyimide" refers to a polymer comprising the following repeating units:

[0072]

[0073] As used herein, the term "polyetherimide" refers to a polymer comprising the following repeating units:

[0074]

[0075] As used herein, the term "polysiloxane" refers to a polymer comprising the following repeating units:

[0076]

[0077] As used herein, the term "polyacrylate" refers to a polymer comprising the following repeating units:

[0078]

[0079] As used herein, the term "polyethylene glycol" refers to a polymer comprising the following repeating units:

[0080]

[0081] As used herein, the term "polyethylene glycol diacrylate" (PEG(DA)) refers to a polymer represented by the following structural formula:

[0082]

[0083] As used herein, the term "polyvinylidene fluoride" refers to a polymer comprising the following repeating units:

[0084]

[0085] As used herein, the term "polytetrahydrofuran" refers to a polymer comprising the following repeating units:

[0086]

[0087] As used herein, the term "polyvinyl butyral" refers to a polymer comprising the following repeating units:

[0088]

[0089] As used herein, the term "poly(acrylonitrile-butadiene-styrene)" refers to a polymer comprising the following repeating units:

[0090]

[0091] As used herein, the term "polyetherpyridine" refers to a polymer comprising the following repeating units:

[0092]

[0093] As used herein, the term "poly(ethyleneimine)" refers to a polymer comprising the following repeating units:

[0094]

[0095] Any of the above polymer repeating units may have one or more hydrogen atoms replaced by -CN, -NO2, -N3, -OH, F, Cl, Br, I, oxo, -SO2H, -SO3H, -OR aa 、-NH(R aa )2、-N(R aa )2、-N(R aa )3 + X - , -SH, -SR aa 、-C(=O)R aa 、-CO2H、-CHO、-CO2R aa 、-OC(=O)R aa 、-OCO2R aa 、-C(=O)N(R aa )2, -OC(=O)N(R aa )2.-NR aa C(=O)R aa 、-NR aa CO2R aa 、-NR aa C(=O)N(R aa )2, -C(=NR aa )R aa 、-C(=O)NR aa S02Raa 、-NR aa S02R aa 、-SO2N(R aa 2. -SO2R aa 、-SO2OR aa 、-OSO2R aa 、-S(=O)R aa 、-OS(=O)R aa 、-Si(R aa )3.-OSi(R aa 3. C 1-12 Alkyl, C 1-12 Alkoxy, C 1-12 Haloalkyl, C 3-12 Cycloalkyl, 3-16 membered heterocyclic group and C 6-12 substituted with aryl, wherein X – is the counter ion and R aa Each instance of is independently selected from H, -OH, C 1-10 Alkyl, C 1-10 Haloalkyl, C 3-12 Cycloalkyl, 5-16 membered heterocyclic group and C 6-12 Aryl, or two R aa The groups are linked to form a 3-16 membered heterocyclic group.

[0096] As used herein, the term "polyol" refers to an alcohol containing more than one hydroxyl group. Examples of polyols include, but are not limited to, ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, glycerol, erythriol, xylitol, hydroquinone, catechol, resorcinol, and phloroglucinol.

[0097] As used herein, the term "polyelectrolyte" refers to a polymer comprising repeating units with charged or ionizable groups. Under a particular set of conditions, a polyelectrolyte has a net negative charge or a net positive charge. In some embodiments, a polyelectrolyte is or comprises a polycation; in some embodiments, a polyelectrolyte is or comprises a polyanion. A polycation has a net positive charge and a polyanion has a net negative charge. The net charge of a given polyelectrolyte may depend on the surrounding chemical conditions, for example, on pH.

[0098] As used herein, the term "perfluorosulfonic acid" refers to a polymer having the following structural formula:

[0099]

[0100] Where R frepresents a perfluoroalkylene or perfluorooxyalkylene group, and x and y represent the relative proportions of perfluoromonomer and sulfonated monomer, respectively. As used herein, the term "perfluoroalkylene" or "perfluorooxyalkylene" refers to an alkylene or oxyalkylene group in which all hydrogen atoms have been replaced by fluorine. One type of PFSA is represented by structural formula (I):

[0101]

[0102] Such PFSAs are usually classified according to the length of their side chains. For example, (Formerly Dow SSC) PFSAs are generally classified as short side chain (SSC) PFSAs, while Considered to be long side chain (LSC) PFSA. Examples of commercially available PFSA include the following:

[0103]

[0104] As used herein, the term "crosslinking" refers to the formation of covalent or ionic bonds between a functional group attached to a polymer backbone and another functional group attached to the same or different backbone, or between a functional group attached to a polymer backbone and a crosslinking agent.

[0105] As used herein, the term "crosslinked polymer" refers to a polymer in which two or more non-adjacent repeating units of the same or different backbones are linked via a crosslinking moiety. The term "crosslinked polymer" also refers to two or more different backbones linked via multiple crosslinking moieties.

[0106] As used herein, the term "crosslinking moiety" refers to a multivalent moiety, such as a divalent or trivalent moiety, that forms a covalent bond with one or more non-adjacent repeating units of the same polymer backbone or with one or more repeating units of different backbones. The crosslinking moiety may comprise a charged group, such as an ammonium group, a metal ion, a carboxylate group, or a sulfate group. In some embodiments, the crosslinking moiety is represented by one of the following structural formulas:

[0107] C 2-6 Alkylene,

[0108] Where: R 1 , R 2 , R 3 , R 4 and R 5 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-14 Aryl and C 6-14 Aryl (C 1-12 Alkylene); R6 is H or -SO3H, R a H or C 1-12 Alkyl; M 2+ Selected from Mr. 2+ , Ca 2+ , Ba 2+ and Al(X) 2+ , wherein X is a halogen, acetate or nitrate; and the symbol Represents the point of attachment of the crosslinking moiety to the repeating unit of the polymer.

[0109] As used herein, the term "crosslinking reaction" refers to a chemical reaction between a functional group attached to a repeating unit of a polymer and a crosslinking agent, which results in the formation of a covalent or electrostatic / ionic bond between the polymer chain and the crosslinking agent. The polymer of the membrane disclosed herein may contain one or more functional groups, including but not limited to NH2, -CN, -NCO, -N3, -OH, F, Cl, Br, I, oxo, -SO2H, -SO3H, -OCO2H, -OCO2Cl, -SH, -CO2H, -CHO, -CO2Cl, C 2-12 Alkenyl and C 2-12 Alkynyl.

[0110] As used herein, the term "conditions sufficient to allow the polymer and the crosslinking agent to undergo a crosslinking reaction" refers to the external stimulus (e.g., heat, UV light, microwave irradiation, the presence of a chemical initiator such as a free radical initiator) and time required to form a crosslinked polymer.

[0111] As used herein, the term "crosslinking degree" in a polymer is defined as the fraction of functional groups attached to all chains of the polymer that have reacted to form crosslinked moieties. In some embodiments, the degree of crosslinking is from about 5% to about 95%, from about 10% to about 80%, from about 20% to about 80%, from about 30% to about 70%, from about 40% to about 60%, from about 30% to about 50%, from about 20% to about 50%, from about 40% to about 70%, from about 20% to about 50%, or from about 10% to about 50%.

[0112] As used herein, the term "gel fraction (%)" is calculated based on the following formula: [[M(f) / [M(i)]]*100, where M(f) is the dry mass of the film exposed to a solvent that dissolves the original polymer and crosslinker, and M(i) is the dry mass of the film before exposure to the dissolving solvent. The gel fraction represents the percentage of polymer and linker remaining in the network after exposure to a solvent that dissolves each individual component.

[0113] In some embodiments, the cross-linked first polymer has a gel fraction of about 50% to about 100%. For example, the cross-linked first polymer has a gel fraction of about 50%, about 60%, about 70%, about 80%, about 90%, or about 100%.

[0114] As used herein, the term "repeat unit" (also called monomer unit) refers to a chemical moiety that repeats itself periodically to produce a complete polymer chain (excluding terminal groups) by linking the repeat units together successively. A polymer may contain one or more different repeat units.

[0115] As used herein, the "backbone" of a polymer or the "backbone" of a polymer is a series of bonded atoms that together produce a continuous chain of molecules. As used herein, the "side chains" of a polymer are a series of bonded atoms that are pendant from the main chain of a polymer.

[0116] As used herein, "PFSA and matrix polymer form an interpenetrating network" refers to a porous matrix containing PFSA in its pores. The porous matrix can be impregnated with PFSA, for example, by soaking the matrix in a solution of PFSA or by spraying a solution of PFSA on the porous matrix. Alternatively, the porous matrix can be impregnated with a solution of PFSA monomers, followed by polymerization within the pores of the matrix.

[0117] As used herein, "unsupported membrane" refers to a membrane containing only a PFSA layer and a layer comprising a metal oxide without any other layers, supports or reinforcements.

[0118] As used herein, the term "continuous layer" refers to a layer that contains no gaps or openings, such that any point on the layer can be connected to any other point on the layer by a straight line, and each point of the straight line belongs to the layer.

[0119] As used herein, the term "glass" refers to an amorphous material that exhibits a glass transition when heated to a liquid state. The atomic structure of glass lacks the long-range periodicity observed in crystalline solids. Due to chemical bonding restrictions, glasses have a high degree of short-range order in terms of local atomic polyhedra. Examples of glasses include, but are not limited to, silicate glasses, soda-lime glasses, aluminates, phosphates, borates, chalcogenides, fluorides, germanates, and metal oxide glasses, such as niobium oxide glasses, tantalum oxide glasses, tungsten oxide glasses, vanadium oxide glasses, or molybdenum oxide glasses.

[0120] As used herein, the term "alkyl" refers to a straight-chain or branched saturated hydrocarbon group having 1 to 10 carbon atoms ("C 1–10 In some embodiments, an alkyl group has 1 to 9 carbon atoms (“C 1–9 In some embodiments, an alkyl group has 1 to 8 carbon atoms (“C 1–8 In some embodiments, an alkyl group has 1 to 7 carbon atoms (“C 1–7 In some embodiments, an alkyl group has 1 to 6 carbon atoms (“C1–6 In some embodiments, an alkyl group has 1 to 5 carbon atoms (“C 1–5 In some embodiments, an alkyl group has 1 to 4 carbon atoms (“C 1–4 In some embodiments, an alkyl group has 1 to 3 carbon atoms (“C 1–3 In some embodiments, an alkyl group has 1 to 2 carbon atoms (“C 1–2 In some embodiments, an alkyl group has 1 carbon atom ("C1 alkyl"). In some embodiments, an alkyl group has 2 to 6 carbon atoms ("C 2–6 C 1-6 Examples of alkyl groups include methyl (C1), ethyl (C2), propyl (C3) (e.g., n-propyl, isopropyl), butyl (C4) (e.g., n-butyl, tert-butyl, sec-butyl, isobutyl), pentyl (C5) (e.g., n-pentyl, 3-pentyl, amyl, neopentyl, 3-methyl-2-butyl, tert-pentyl) and hexyl (C6) (e.g., n-hexyl). Additional examples of alkyl groups include n-heptyl (C7), n-octyl (C8), etc. Unless otherwise specified, each instance of an alkyl group is independently unsubstituted ("unsubstituted alkyl") or substituted ("substituted alkyl") with one or more substituents (e.g., halogen, such as F). In certain embodiments, an alkyl group is an unsubstituted C 1-10 Alkyl (such as unsubstituted C 1-6 Alkyl, for example, -CH3(Me), unsubstituted ethyl (Et), unsubstituted propyl (Pr, for example, unsubstituted n-propyl (n-Pr), unsubstituted isopropyl (i-Pr)), unsubstituted butyl (Bu, for example, unsubstituted n-butyl (n-Bu), unsubstituted tert-butyl (tert-Bu or t-Bu), unsubstituted sec-butyl (sec-Bu), unsubstituted isobutyl (i-Bu)). In certain embodiments, the alkyl group is substituted C 1-10 Alkyl (such as substituted C 1-6 Alkyl, e.g., -CF3, Bn).

[0121] As used herein, the term "alkenyl" refers to a straight or branched chain hydrocarbon group ("C 2-10 In some embodiments, an alkenyl group has 2 to 9 carbon atoms ("C 2-9 In some embodiments, an alkenyl group has 2 to 8 carbon atoms (“C 2-8In some embodiments, an alkenyl group has 2 to 7 carbon atoms (“C 2-7 In some embodiments, an alkenyl group has 2 to 6 carbon atoms (“C 2-6 In some embodiments, an alkenyl group has 2 to 5 carbon atoms (“C 2-5 In some embodiments, an alkenyl group has 2 to 4 carbon atoms (“C 2-4 In some embodiments, an alkenyl group has 2 to 3 carbon atoms (“C 2-3 In some embodiments, an alkenyl group has 2 carbon atoms ("C2 alkenyl"). The one or more carbon-carbon double bonds may be internal (such as in 2-butenyl) or terminal (such as in 1-butenyl). 2–4 Examples of alkenyl groups include, but are not limited to, ethenyl (C2), 1-propenyl (C3), 2-propenyl (C3), 1-butenyl (C4), 2-butenyl (C4), etc. 2–6 Examples of the alkenyl group include the aforementioned C 2–4 In some embodiments, the alkenyl group is an unsubstituted C 1-1, ... 2-10 In certain embodiments, the alkenyl group is a substituted C 2-10 Alkenyl.

[0122] As used herein, the term "alkynyl" refers to a straight or branched chain hydrocarbon group ("C 2-10 In some embodiments, an alkynyl group has 2 to 9 carbon atoms ("C 2–9 In some embodiments, an alkynyl group has 2 to 8 carbon atoms (“C 2–8 In some embodiments, an alkynyl group has 2 to 7 carbon atoms (“C 2–7 In some embodiments, an alkynyl group has 2 to 6 carbon atoms (“C 2–6 In some embodiments, an alkynyl group has 2 to 5 carbon atoms (“C 2–5 In some embodiments, an alkynyl group has 2 to 4 carbon atoms (“C 2–4 In some embodiments, an alkynyl group has 2 to 3 carbon atoms (“C 2–3In some embodiments, an alkynyl group has 2 carbon atoms ("C2 alkynyl"). The one or more carbon-carbon triple bonds can be internal (such as in 2-butynyl) or terminal (such as in 1-butynyl). C 2–4 Examples of alkynyl groups include, but are not limited to, ethynyl (C2), 1-propynyl (C3), 2-propynyl (C3), 1-butynyl (C4), 2-butynyl (C4), and the like. 2–6 Examples of the alkynyl group include the aforementioned C 2–4 In some embodiments, the alkynyl group is an unsubstituted C alkynyl group, and pentynyl (C5), hexynyl (C6), and the like. Additional examples of alkynyl groups include heptynyl (C7), octynyl (C8), and the like. Unless otherwise specified, each instance of an alkynyl group is independently unsubstituted (an “unsubstituted alkynyl”) or substituted (a “substituted alkynyl”) with one or more substituents. In certain embodiments, an alkynyl group is an unsubstituted C 2-10 In certain embodiments, the alkynyl group is a substituted C 2-10 Alkynyl.

[0123] The term "aryl" refers to a group having 6-14 ring carbon atoms and zero heteroatoms provided in the aromatic ring system, a monocyclic or polycyclic (e.g., bicyclic or tricyclic) 4n+2 aromatic ring system (e.g., having 6, 10, or 14 π electrons in common in the ring array) ("C 6-14 In some embodiments, an aryl group has 6 ring carbon atoms ("C6 aryl"; e.g., phenyl). In some embodiments, an aryl group has 10 ring carbon atoms ("C 10 In some embodiments, an aryl group has 14 ring carbon atoms ("C 14 "Aryl" also includes ring systems in which an aryl ring as defined above is fused to one or more carbocyclyl or heterocyclyl groups, wherein the radical or point of attachment is on the aryl ring, and in such cases the number of carbon atoms continues to refer to the number of carbon atoms in the aryl ring system. Unless otherwise specified, each instance of an aryl group is independently unsubstituted (an "unsubstituted aryl") or substituted (a "substituted aryl") with one or more substituents. In certain embodiments, an aryl group is an unsubstituted C 6-14 In certain embodiments, the aryl group is a substituted C 6-14 Aryl.

[0124] The term "haloalkyl" refers to a substituted alkyl group in which one or more hydrogen atoms are independently replaced by a halogen, e.g., fluorine, bromine, chlorine, or iodine. In some embodiments, the haloalkyl moiety has 1 to 12 carbon atoms ("C 1-12In some embodiments, the haloalkyl moiety has 1 to 6 carbon atoms (“C 1-6 In some embodiments, the haloalkyl moiety has 1 to 4 carbon atoms (“C 1-4 In some embodiments, the haloalkyl moiety has 1 to 3 carbon atoms (“C 1-3 In some embodiments, the haloalkyl moiety has 1 to 2 carbon atoms (“C 1-2 "haloalkyl"). Examples of haloalkyl groups include -CHF2, -CH2F, -CF3, -CH2CF3, -CF2CF3, -CF2CF2CF3, -CCl3, -CFCl2, -CF2Cl, and the like.

[0125] The term "sulfonic acid group" refers to the following group: -S(O)2OH.

[0126] The term "sulfonate" refers to a salt or ester of a sulfonic acid, -S(O)2OR, wherein R represents a cation, such as a metal or ammonium cation, or an aliphatic or aromatic substituent. Examples of sulfonates include salts such as lithium sulfonate, sodium sulfonate, potassium sulfonate, or ammonium sulfonate. In some embodiments, the term "sulfonate" refers to an ester of a sulfonic acid, for example, an optionally substituted C 1-12 Alkyl sulfonate or optionally substituted C 6-12 In some embodiments, R is a multivalent (e.g., divalent or trivalent) group that forms a covalent or ionic bond with one or more sulfonic acid groups attached to the same or different sulfonated polymer chains, thereby forming a crosslinking moiety together with the two or more -S(O)2O- groups to which it is attached.

[0127] The term "sulfonamide" refers to the amide of a sulfonic acid, -S(O)2NRR', wherein R and R' are each hydrogen or an optionally substituted aliphatic or aromatic substituent, such as an optionally substituted C 1-12 Alkyl or optionally substituted C 6-12 In some embodiments, R and / or R' are each a multivalent (e.g., divalent or trivalent) group that forms a covalent or ionic bond with one or more sulfonic acid groups attached to the same or different sulfonated polymer chains, thereby forming a crosslinking moiety together with the two or more -S(O)2O- groups to which it is attached.

[0128] Adding the suffix "-ene" to a group indicates that the group is a divalent moiety, for example, alkylene is a divalent moiety of an alkyl group, alkenylene is a divalent moiety of an alkenyl group, alkynylene is a divalent moiety of an alkynyl group, and arylene is a divalent moiety of an aryl group.

[0129] The term "substituted" refers to a moiety with a substituent that replaces hydrogen on one or more carbons of the skeleton. It should be understood that "replacement" or "substituted by..." includes implicit conditions, i.e., such substitution is consistent with the allowed valence of the substituted atom and the substituent, and the substitution produces a stable compound, for example, a compound that does not spontaneously undergo transformation, such as by rearrangement, cyclization, elimination, etc. As used herein, the term "substituted" is contemplated to include all allowed substituents of organic compounds. In a broad sense, allowed substituents include acyclic and cyclic, branched and unbranched, carbocyclic and heterocyclic, aromatic and non-aromatic substituents of organic compounds. For appropriate organic compounds, allowed substituents may be one or more and the same or different. For purposes of the present invention, heteroatoms such as nitrogen may have hydrogen substituents and / or any allowed substituents of organic compounds described herein that satisfy the valence of heteroatoms. Substituents may include any substituent described herein, for example, halogen, hydroxyl, carbonyl (such as carboxyl, alkoxycarbonyl, formyl or acyl), thiocarbonyl (such as thioester, thioacetate or thioformate), alkoxy, phosphoryl, phosphate, phosphonate, phosphinate, amino, amido, amidino, imino, cyano, nitro, azido, sulfhydryl, alkylthio, sulfate, sulfonate, sulfamoyl, sulfonamido, sulfonyl, heterocyclyl, aralkyl or aromatic or heteroaromatic moiety. It will be appreciated by those skilled in the art that the substituents themselves may be substituted if appropriate. Unless explicitly stated as "unsubstituted", references to chemical moieties herein are understood to include substituted variants. For example, references to "aryl" groups or moieties implicitly include both substituted and unsubstituted variants.

[0130] Exemplary carbon atom substituents include, but are not limited to, halogen, -CN, -NO2, -N3, -OH, F, Cl, Br, I, oxo, -SO2H, -SO3H, -OR aa 、-NH(R aa )2、-N(R aa )2、-N(R aa )3 + X - , -SH, -SR aa 、-C(=O)R aa 、-CO2H、-CHO、-CO2R aa 、-OC(=O)R aa 、-OCO2R aa 、-C(=O)N(R aa )2, -OC(=O)N(R aa )2.-NR aa C(=O)R aa 、-NR aa CO2R aa 、-NRaa C(=O)N(R aa )2, -C(=NR aa )R aa 、-C(=O)NR aa S02R aa 、-NR aa S02R aa 、-SO2N(R aa 2. -SO2R aa 、-SO2OR aa 、-OSO2R aa 、-S(=O)R aa 、-OS(=O)R aa 、-Si(R aa )3.-OSi(R aa 3. C 1-12 Alkyl, C 1-12 Haloalkyl, 3-16 membered heterocyclic group and C 6-12 Aryl, wherein X – is the counter ion and R aa Each instance of is independently selected from H, -OH, C 1-10 Alkyl, C 1-10 Haloalkyl, C 3-12 Cycloalkyl, 5-16 membered heterocyclic group and C 6-12 Aryl, or two R aa The groups are linked to form a 3-16 membered heterocyclic group.

[0131] In a first embodiment, the present invention is a bilayer polyelectrolyte membrane comprising: a first layer disposed on a second layer, wherein: the first layer comprises a perfluorosulfonic acid (PFSA) polymer, and the second layer comprises a crystalline metal oxide.

[0132] In a first aspect of the first embodiment, the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0133]

[0134] wherein x is an integer between 1 and 15, m is an integer between 0 and 2, n is an integer between 1 and 5, and represents the connection point to the adjacent repeating unit. For example, x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3. In some cases, m is 1 and n is 2.

[0135] In a second aspect of the first embodiment, the PFSA is a polymer comprising about 500 to about 1500 repeating units represented by structural formula (I). For example, the PFSA is a polymer comprising about 600 to about 1400, about 700 to about 1300, about 800 to about 1200, or about 900 to about 1100 repeating units represented by structural formula (I). For example, the PFSA is a polymer comprising about 1000 repeating units represented by structural formula (I). The remaining features and exemplary features of the second aspect are as described above with respect to the first aspect of the first embodiment.

[0136] In a third aspect of the first embodiment, the metal oxide comprises a reducible metal oxide. For example, the metal oxide comprises, for example, consists of, titanium oxide, zirconium oxide, hafnium oxide, vanadium oxide, niobium oxide, tantalum oxide, chromium oxide, molybdenum oxide, tungsten oxide, manganese oxide, iron oxide, cobalt oxide, nickel oxide, cerium oxide, gadolinium oxide and samarium oxide or a combination thereof. For example, the metal oxide comprises titanium oxide, zirconium oxide, niobium oxide and cerium oxide or a combination thereof. For example, the metal oxide comprises titanium oxide, manganese oxide, niobium oxide and cerium oxide or a combination thereof. For example, the metal oxide comprises cerium oxide, for example, consists of cerium oxide. For example, the metal oxide is cerium oxide. For example, the metal oxide is zirconium oxide. For example, the metal oxide is manganese oxide. For example, the metal oxide is cerium oxide, zirconium oxide or manganese oxide. The remaining features and exemplary features of the third aspect are as described above with respect to the first and second aspects of the first embodiment.

[0137] In a fourth aspect of the first embodiment, the metal oxide is doped with one or more dopants. For example, the metal oxide doped with one or more dopants is selected from gadolinium-doped cerium oxide, samarium-doped cerium oxide, niobium-doped titanium oxide, or cerium-doped zirconium oxide. For example, the dopant is selected from Si, In, Bi, Al, Y, Ga, Pb, Sn, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, La, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. For example, the metal oxide comprises about 0.5 wt % to about 5 wt % of the dopant, such as about 0.5 wt %, about 1 wt %, about 1.5 wt %, about 2 wt %, about 2.5 wt %, about 3 wt %, about 3.5 wt %, about 4.5 wt %, about 4.5 wt %, or about 5.0 wt %. The remaining features and exemplary features of the fourth aspect are as described above with respect to the first to third aspects of the first embodiment.

[0138] In the fifth aspect of the first embodiment, the metal oxide is in the form of crystalline particles with a characteristic size of about 1nm to about 100nm. For example, the metal oxide is in the form of crystalline particles with a characteristic size of about 1nm, about 2nm, about 3nm, about 4nm, about 5nm, about 6nm, about 7nm, about 8nm, about 9nm, about 10nm, about 12nm, about 14nm, about 16nm, about 18nm, about 20nm, about 25nm, about 30nm, about 35nm, about 40nm, about 45nm, about 50nm, about 60nm, about 70nm, about 80nm, about 690nm or about 100nm. For example, the metal oxide is in the form of crystalline particles with a characteristic size of about 2nm to about 50nm, about 3nm to about 30nm or about 4nm to about 20nm. For example, the metal oxide is in the form of crystalline particles with a characteristic size of about 2nm to about 10nm. For example, the metal oxide is in the form of crystalline particles with a characteristic size of about 4nm. The remaining features and exemplary features of the fifth aspect are as described above with respect to the first to fourth aspects of the first embodiment.

[0139] In a sixth aspect of the first embodiment, the second layer also comprises a polymer matrix, and the metal oxide is dispersed in the polymer matrix.For example, the second layer comprises about 5 % by weight to about 85 % by weight of metal oxide.For example, the second layer comprises about 10 % by weight to about 85 % by weight of metal oxide, about 15 % by weight to about 85 % by weight of metal oxide, about 20 % by weight to about 85 % by weight of metal oxide, about 25 % by weight to about 85 % by weight of metal oxide, about 30 % by weight to about 85 % by weight of metal oxide, about 35 % by weight to about 85 % by weight of metal oxide, about 40 % by weight to about 85 % by weight of metal oxide, about 45 % by weight to about 85 % by weight of metal oxide, about 50 % by weight to about 85 % by weight of metal oxide, about 55 % by weight to about 85 % by weight of metal oxide, about 60 % by weight to about 85 % by weight of metal oxide, about 65 % by weight to about 85 % by weight of metal oxide, about 70 % by weight to about 85 % by weight of metal oxide or about 75 % by weight to about 85 % by weight of metal oxide. For example, the second layer comprises about 10% by weight of metal oxide, about 15% by weight, about 20% by weight, about 25% by weight, about 30% by weight of metal oxide, about 35% by weight of metal oxide, about 40% by weight of metal oxide, about 45% by weight of metal oxide, about 50% by weight of metal oxide, about 55% by weight of metal oxide, about 60% by weight of metal oxide, about 65% by weight of metal oxide, about 70% by weight of metal oxide or about 75% by weight of metal oxide. For example, the second layer comprises about 30% by weight to about 45% by weight of metal oxide. The remaining features and exemplary features of the sixth aspect are as described above with respect to the first to fifth aspects of the first embodiment.

[0140] In a seventh aspect of the first embodiment, the polymer matrix includes one or more first polymers selected from polyether, polysulfonate, polysulfone, polyimidazole, polysiloxane, polyacrylate, polysulfide, polyolefin, polyamide, polytriazole, benzimidazole, polyester and polycarbonate. For example, the one or more first polymers are selected from polyethylene glycol (PEG), polyetheretherketone (PEEK), polytetrahydrofuran, polyvinyl butyral, poly (acrylonitrile-butadiene-styrene), polyetherpyridine, polyphenylsulfone (PPS), polyphosphazene (POP), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene oxide (PPO), polyaryletherketone (PAEK), polysulfone, polythioethersulfone, polyimide (PI), polyetherimide (PEI), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and polyamine. For example, the one or more first polymers are selected from PEG, PEEK, PPS, PBI and PVDF. For example, the one or more first polymers are selected from PEG, PPS, poly(ethyleneimine) and PVDF. For example, the one or more first polymers include PEG. For example, the first polymer is PEG. For example, the first polymer is PEG diacrylate. The remaining features and exemplary features of the seventh aspect are as described above for the first to sixth aspects of the first embodiment.

[0141] In an eighth aspect of the first embodiment, the one or more first polymers have a molecular weight of about 250,000 g / mol to about 4,000,000 g / mol, such as about 500,000 g / mol to about 1,000,000 g / mol. For example, the one or more first polymers have a molecular weight of about 300,000 g / mol, about 400,000 g / mol, about 500,000 g / mol, about 600,000 g / mol, about 700,000 g / mol, about 800,000 g / mol, about 900,000 g / mol, about 1,000,000 g / mol, about 1,500,000 g / mol, about 2,000,000 g / mol, about 2,500,000 g / mol, about 3,000,000 g / mol, or about 3,500,000 g / mol. The remaining features and exemplary features of the eighth aspect are as described above with respect to the first to seventh aspects of the first embodiment.

[0142] In a ninth aspect of the first embodiment, the one or more first polymers are sulfonated. For example, the first polymer is sulfonated PPS (sPPS). The remaining features and exemplary features of the ninth aspect are as described above with respect to the first to eighth aspects of the first embodiment.

[0143] In a tenth aspect of the first embodiment, at least one of the one or more first polymers is cross-linked. For example, at least one of the one or more first polymers comprises a cross-linking portion represented by one of the following structural formulas: 2-6 Alkylene,

[0144] Where: R 1 , R 2 , R 3 , R 4 and R 5 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-14 Aryl and C 6-14 Aryl (C 1-12 Alkylene); R a H or C 1-12 Alkyl; M 2+ Selected from Mr. 2+ , Ca 2+ , Ba 2+ and Al(X) 2+ , wherein X is a halogen, acetate or nitrate; and the symbol Represents the connection point of the cross-linking moiety to the repeating unit of the one or more first polymers. For example, the cross-linking moiety is represented by one of the following structural formulas:

[0145] For example, the cross-linking moiety is represented by one of the following structural formulas: For example, the cross-linking moiety is represented by one of the following structural formulas:

[0146] For example, the cross-linking moiety is represented by one of the following structural formulas: For example, the cross-linking portion has a structure of For example, the first polymer is polyethyleneimine and the crosslinking portion is represented by a structure of represent.

[0147] For example, the cross-linking moiety is represented by the following structural formula: For example, the cross-linking moiety is represented by the following structural formula: For example, the first polymer is PEG(DA) and the cross-linking portion is represented by the following structural formula: The remaining features and exemplary features of the tenth aspect are as described above with respect to the first to ninth aspects of the first embodiment.

[0148] In an eleventh aspect of the first embodiment, the first layer further comprises a porous matrix comprising a matrix polymer, wherein the PFSA and the matrix polymer form an interpenetrating network. For example, the first layer comprises about 50 wt % to about 99 wt % PFSA, about 55 wt % to about 98 wt % PFSA, about 60 wt % to about 97 wt % PFSA, about 70 wt % to about 96 wt % PFSA, or about 80 wt % to about 96 wt % PFSA. For example, the first layer comprises about 70 wt % to about 99 wt % PFSA, such as about 78 wt % to about 95 wt % PFSA. The remaining features and exemplary features of the eleventh aspect are as described above with respect to the first to tenth aspects of the first embodiment.

[0149] In a twelfth aspect of the first embodiment, the matrix polymer is polytetrafluoroethylene (PTFE). For example, the matrix polymer is expanded PTFE (ePTFE). The remaining features and exemplary features of the twelfth aspect are as described above with respect to the first to eleventh aspects of the first embodiment.

[0150] In a thirteenth aspect of the first embodiment, the one or more first polymers have a gel fraction of about 50% to about 100%. For example, the gel fraction is about 50%, about 60%, about 70%, about 80%, about 90%, or about 100%. The remaining features and exemplary features of the thirteenth aspect are as described above for the first to twelfth aspects of the first embodiment.

[0151] In the fourteenth aspect of the first embodiment, the first layer is about 5 μm to about 200 μm thick. For example, the first layer is about 5 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, about 40 μm, about 45 μm, about 50 μm, about 55 μm, about 60 μm, about 65 μm, about 70 μm, about 75 μm, about 80 μm, about 85 μm, about 90 μm, about 95 μm, about 100 μm, about 110 μm, about 120 μm, about 130 μm, about 140 μm, about 150 μm, about 160 μm, or about 170 μm, about 180 μm, about 190 μm or about 200 μm thick. For example, the first layer is about 5 μm to about 175 μm thick. For example, the first layer is about 25 μm thick.The remaining features and exemplary features of the fourteenth aspect are as described above with respect to the first to thirteenth aspects of the first embodiment.

[0152] In a fifteenth aspect of the first embodiment, the second layer has a thickness of about 0.2 μm to about 175 μm. For example, the thickness of the second layer is about 0.2 μm, about 0.4 μm, about 0.6 μm, about 0.8 μm, about 1.0 μm, about 2.0 μm, about 3.0 μm, about 4.0 μm, about 5 μm, about 10 μm, about 15 μm, about 20 μm, about 25 μm, about 30 μm, about 35 μm, about 40 μm, about 45 μm, about 50 μm, about 55 μm, about 60 μm, about 65 μm, about 70 μm, about 75 μm, about 80 μm, about 85 μm, about 90 μm, about 95 μm, about 100 μm, about 110 μm, about 120 μm, about 130 μm, about 140 μm, about 150 μm, about 160 μm or about 170 μm. For example, the thickness of the second layer is about 0.2 μm to about 10 μm, about 0.4 μm to about 5 μm, about 0.6 μm to about 2 μm, about 0.8 μm to about 1.5 μm. For example, the thickness of the second layer is about 1 μm. For example, the second layer is about 0.5 μm to about 1 μm thick. For example, the second layer is about 0.7 μm thick. The remaining features and exemplary features of the fifteenth aspect are as described above with respect to the first to fourteenth aspects of the first embodiment.

[0153] In a sixteenth aspect of the first embodiment, the first layer is continuous. The remaining features and exemplary features of the sixteenth aspect are as described above with respect to the first to fifteenth aspects of the first embodiment.

[0154] In a seventeenth aspect of the first embodiment, the membrane is unsupported. The remaining features and exemplary features of the seventeenth aspect are as described above with respect to the first to sixteenth aspects of the first embodiment.

[0155] In an eighteenth aspect of the first embodiment, the first layer consists of PFSA, wherein the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0156]

[0157] Wherein: x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; the metal oxide is CeO2, and the second layer further comprises a layer having the following structural formula The remaining features and exemplary features of the eighteenth aspect are as described above with respect to the first to seventeenth aspects of the first embodiment.

[0158] In a nineteenth aspect of the first embodiment, the second layer further comprises glass, and the metal oxide is dispersed in the glass. For example, the glass comprises niobium oxide, silicon dioxide, tantalum oxide, tungsten oxide, vanadium oxide, or molybdenum oxide. The remaining features and exemplary features of the nineteenth aspect are as described above with respect to the first to eighteenth aspects of the first embodiment.

[0159] In a twentieth aspect of the first embodiment, the degree of sulfonation of the first polymer is from about 100% to about 400%. For example, the degree of sulfonation of the first polymer is from about 10% to about 100%, from about 20% to about 100%, from about 30% to about 100%, from about 40% to about 100%, from about 50% to about 100%, from about 60% to about 100%, from about 70% to about 100%, from about 80% to about 100%, from about 50% to about 200%, from about 80% to about 200%, from about 100% to about 200%, from about 100% to about 250%. , about 150% to about 200%, about 100% to about 300%, about 100% to about 350%, about 100% to about 400%, about 150% to about 250%, about 150% to about 300%, about 150% to about 350%, about 150% to about 400%, about 200% to about 300%, about 200% to about 350%, about 200% to about 400%, or about 250% to about 350%. For example, the first polymer has a degree of sulfonation of about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, about 100%, about 120%, about 140%, about 160%, about 180%, about 200%, about 220%, about 240%, about 260%, about 280%, about 300%, about 320%, about 340%, about 360%, about 380%, or about 400%. For example, the first polymer has a degree of sulfonation of about 100% to about 300%. For example, the first polymer has a degree of sulfonation of about 200%. For example, the first polymer has an average of about 1 to about 3 sulfonic acid, sulfonate / ester, and sulfonamide groups per repeating unit. For example, the first polymer has an average of about 2 sulfonic acid, sulfonate / ester, and sulfonamide groups per repeating unit. The remaining features and exemplary features of the twentieth aspect are as described above with respect to the first to nineteenth aspects of the first embodiment.

[0160] In the twenty-first aspect of the first embodiment, the crosslinking degree of the first polymer is about 10% to about 95%. For example, the crosslinking degree of the first polymer is about 15% to about 90%, about 20% to about 80%, about 20% to about 70%, about 20% to about 60%, about 20% to about 50%, about 20% to about 45%, about 20% to about 40%, about 30% to about 50%, about 25% to about 30% or about 30% to about 35%. For example, the crosslinking degree of the first polymer is about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90% or about 95%. For example, the crosslinking degree of the first polymer is about 70%. For example, the crosslinking degree of the first polymer is about 40%. The remaining features and exemplary features of the twenty-first aspect are as described above with respect to the first to twentieth aspects of the first embodiment.

[0161] In a twenty-second aspect of the first embodiment, the first layer consists of PFSA, wherein the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0162]

[0163] in:

[0164] x is an integer between 5 and 14,

[0165] m is 1 or 2, and

[0166] n is 2 or 3;

[0167] The metal oxide is CeO2, and

[0168] The second layer also comprises a cross-linked PEG (DA) comprising a cross-linking moiety represented by the following structural formula:

[0169] For example, the membrane is unsupported, the crystalline particles of CeO2 have a characteristic size of about 4 nm, and the degree of crosslinking of the crosslinked PEG (DA) is about 70%. The remaining features and exemplary features of the twenty-second aspect are as described above with respect to the first to twenty-first aspects of the first embodiment.

[0170] In a twenty-third aspect of the first embodiment, the membrane is unsupported. The PFSA is a polymer comprising repeating units represented by structural formula (I):

[0171]

[0172] in

[0173] x is an integer between 5 and 14,

[0174] m is 1 or 2, and

[0175] n is 2 or 3; and further wherein

[0176] The metal oxide is CeO2,

[0177] The second layer also comprises a cross-linked sPPS having a cross-linked moiety represented by the following structural formula:

[0178] The sPPS has a sulfonation degree of about 200%, and

[0179] The degree of cross-linking of the sPPS is about 40%.

[0180] The remaining features and exemplary features of the twenty-third aspect are as described above with respect to the first to twenty-second aspects of the first embodiment.

[0181] In a twenty-fourth aspect of the first embodiment, the membrane is unsupported, and the PFSA is a polymer comprising repeating units represented by structural formula (I):

[0182]

[0183] in

[0184] x is an integer between 5 and 14,

[0185] m is 1 or 2, and

[0186] n is 2 or 3; and further wherein

[0187] The metal oxide is CeO2,

[0188] The second layer also comprises a cross-linked sPPS comprising a cross-linked moiety represented by one of the following structural formulas:

[0189] The sPPS has a sulfonation degree of about 200%, and

[0190] The sPPS has a cross-linking degree of about 25% to about 30%.

[0191] The remaining features and exemplary features of the twenty-fourth aspect are as described above with respect to the first to twenty-third aspects of the first embodiment.

[0192] In a second embodiment, the present invention is a method for manufacturing a double-layer polyelectrolyte membrane described herein with respect to the first embodiment and its various aspects, the method comprising: providing a first layer having a first side, and a suspension comprising a metal oxide and a solvent; and coating the first side of the first layer with the suspension to produce a coated first layer.

[0193] In the first aspect of the second embodiment, suspension comprises the metal oxide of about 0.01 volume % to about 74 volume %.For example, suspension comprises the metal oxide of about 0.01 volume % to about 1 volume %, such as the metal oxide of about 0.05 volume % to about 1 volume %, about 0.1 volume % to about 0.8 volume %, about 0.2 volume % to about 0.6 volume % or about 0.05 volume % to about 0.5 volume %.For example, suspension comprises the metal oxide of about 0.4 volume %.For example, suspension comprises the metal oxide of about 1 volume % to about 74 volume %, such as the metal oxide of about 1 volume % to about 74 volume %, about 10 volume % to about 70 volume %, about 15 volume % to about 65 volume %, about 20 volume % to about 60 volume %, about 25 volume % to about 55 volume % or about 30 volume % to about 50 volume %.For example, suspension comprises the metal oxide of about 35 volume %.

[0194] In the second aspect of the second embodiment, suspension also includes the first polymer.For example, suspension includes the first polymer of about 0.2 % by weight to about 25 % by weight, for example, the first polymer of about 0.5 % by weight.For example, suspension includes the first polymer of about 0.2 % by weight, about 0.3 % by weight, about 0.4 % by weight, about 0.6 % by weight, about 0.7 % by weight, about 0.8 % by weight, about 0.9 % by weight, about 1.0 % by weight, about 2 % by weight, about 3 % by weight, about 4 % by weight, about 5 % by weight, about 6 % by weight, about 7 % by weight, about 8 % by weight, about 9 % by weight, about 10 % by weight, about 15 % by weight or about 20 % by weight.The remaining features and example features of the second aspect are as described above about the first aspect of the second embodiment.

[0195] In a third aspect of the second embodiment, the first polymer comprises a crosslinkable group. For example, the crosslinkable group is selected from OH, NH2, NH, SH, C(O)OH, C(O)Cl, C(O)Br, NHNH2, N3, S(O)2OH, S(O)2Cl, -NCO, For example, the crosslinkable group is selected from OH, NH2, SH, C(O)OH, C(O)Cl, C(O)Br, NHNH2, N3, S(O)2OH, S(O)2Cl, -NCO, For example, the crosslinkable group is For example, the crosslinkable group is NH. For example, the crosslinkable group is S(O)2OH. The remaining features and exemplary features of the third aspect are as described above with respect to the first to second aspects of the second embodiment.

[0196] In a fourth aspect of the second embodiment, the suspension further comprises a crosslinking initiator. For example, the crosslinking initiator is selected from 2,2-dimethoxy-2-phenylacetophenone (DMPA), azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO). The remaining features and exemplary features of the fourth aspect are as described above for the first to third aspects of the second embodiment.

[0197] In a fifth aspect of the second embodiment, the method further comprises a step of crosslinking the first polymer under conditions sufficient to cause the crosslinking initiator to initiate crosslinking of the first polymer. For example, the conditions sufficient to cause the crosslinking initiator to initiate crosslinking of the first polymer include visible light irradiation, UV light irradiation, application of heat, microwave irradiation, ultrasound or gamma ray irradiation. The remaining features and exemplary features of the fifth aspect are as described above with respect to the first to fourth aspects of the second embodiment.

[0198] In a sixth aspect of the second embodiment, suspension comprises a crosslinking initiator of about 0.5 % by weight to about 50 % by weight. For example, suspension comprises a crosslinking initiator of about 5 % by weight to about 15 % by weight. For example, suspension comprises a crosslinking initiator of about 0.2 % by weight, about 0.3 % by weight, about 0.4 % by weight, about 0.6 % by weight, about 0.7 % by weight, about 0.8 % by weight, about 0.9 % by weight, about 1.0 % by weight, about 2 % by weight, about 3 % by weight, about 4 % by weight, about 5 % by weight, about 6 % by weight, about 7 % by weight, about 8 % by weight, about 9 % by weight, about 10 % by weight, about 15 % by weight or about 20 % by weight. The remaining features and exemplary features of the sixth aspect are as described above about the first to the fifth aspect of the second embodiment.

[0199] In the seventh aspect of the second embodiment, the suspension also includes a cross-linking agent. For example, the cross-linking agent is selected from a polyol, an aldehyde, an amine, an epoxide, a thiol or a compound comprising a terminal olefin or an alkyne. For example, the cross-linking agent is selected from glycerol, ethylene glycol, hydroquinone, 2,5-dihydroxybenzene sulfonic acid, 2,5-dihydroxybenzene-1,4-disulfonic acid, biphenyl, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol and tetrafluorostyrene. For example, the cross-linking agent is selected from glycerol, ethylene glycol, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol, glutaraldehyde, styrene and tetrafluorostyrene. For example, the cross-linking agent is a polyol, such as glycerol or ethylene glycol. For example, the cross-linking agent is hydroquinone or 2,5-dihydroxybenzene sulfonic acid. The remaining features and exemplary features of the seventh aspect are as described above for the first to sixth aspects of the second embodiment.

[0200] In the eighth aspect of the second embodiment, the conditions sufficient to cause the first polymer and the cross-linking agent to undergo a cross-linking reaction include heating the coated first layer to a cross-linking temperature of about 150°C to about 200°C for a cross-linking time of about 2 hours to about 96 hours. For example, the cross-linking temperature is about 150°C, about 160°C, about 170°C, about 180°C, about 190°C, or about 200°C. For example, the cross-linking temperature is about 180°C, and the cross-linking time is about 4 hours. For example, the cross-linking time is about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, about 10 hours, about 20 hours, about 30 hours, about 40 hours, about 50 hours, about 60 hours, about 70 hours, about 80 hours, or about 90 hours. For example, the cross-linking time is about 4 hours. The remaining features and exemplary features of the eighth aspect are as described above with respect to the first to seventh aspects of the second embodiment.

[0201] In a ninth aspect of the second embodiment, coating the first side of the first layer with a suspension comprises spraying, spin coating, drop coating, zone casting, dip coating, blade coating, printing, vacuum filtration, slot die coating, curtain coating or a combination thereof. For example, coating the first side of the first layer with a suspension comprises spraying. The remaining features and exemplary features of the ninth aspect are as described above with respect to the first to eighth aspects of the second embodiment.

[0202] In the tenth aspect of the second embodiment, the solvent is selected from dimethylformamide, tetrahydrofuran, N-methylformamide, formamide, acetonitrile, dimethylacetamide, propylene carbonate, ethylene carbonate, N-methyl pyrrolidone, dimethyl sulfoxide or a combination thereof. For example, the solvent is dimethylformamide. The remaining features and exemplary features of the tenth aspect are as described above for the first to ninth aspects of the second embodiment.

[0203] In a third embodiment, the present invention is a membrane electrode assembly (MEA) comprising: a double-layer polyelectrolyte membrane as described herein with respect to the first embodiment and its various aspects; a cathode; and an anode, wherein the double-layer electrolyte membrane is disposed between the anode and the cathode.

[0204] In the first aspect of the third embodiment, the cathode is disposed on the first layer of the double-layer electrolyte membrane, and the anode is disposed on the second layer of the double-layer electrolyte membrane. Alternatively, the anode is disposed on the first layer of the double-layer electrolyte membrane, and the cathode is disposed on the second layer of the double-layer electrolyte membrane.

[0205] In a fourth embodiment, the invention is a fuel cell comprising one or more MEAs described herein with respect to the third embodiment and various aspects thereof and one or more gas flow bipolar plates.

[0206] In various embodiments, the present invention is

[0207] 1. A double-layer polyelectrolyte membrane, comprising:

[0208] A first layer, the first layer being disposed on a second layer, wherein:

[0209] The first layer comprises a perfluorosulfonic acid (PFSA) polymer, and

[0210] The second layer comprises a crystalline metal oxide.

[0211] 2. The double-layer polyelectrolyte membrane according to claim 1, wherein the PFSA polymer comprises a repeating unit represented by structural formula (I):

[0212]

[0213] in:

[0214] x is an integer between 1 and 15,

[0215] m is an integer between 0 and 2,

[0216] n is an integer between 1 and 5, and

[0217] symbol Represents the point of attachment to the adjacent repeat unit.

[0218] 3. The double-layer polyelectrolyte membrane according to claim 2, wherein:

[0219] x is an integer between 5 and 14,

[0220] m is 1 or 2, and

[0221] n is 2 or 3.

[0222] 4. The double-layer polyelectrolyte membrane according to claim 2 or 3, wherein the PFSA polymer comprises about 900 to about 1100 repeating units represented by structural formula (I).

[0223] 5. The double-layer polyelectrolyte membrane according to any one of claims 1 to 4, wherein the metal oxide comprises a reducible metal oxide.

[0224] 6. A double-layer polyelectrolyte membrane according to any one of claims 1-5, wherein the metal oxide comprises titanium oxide, zirconium oxide, hafnium oxide, vanadium oxide, niobium, tantalum oxide, chromium oxide, molybdenum oxide, tungsten oxide, manganese oxide, iron oxide, cobalt oxide, nickel oxide, cerium oxide, gadolinium oxide and samarium oxide or a combination thereof.

[0225] 7 . The double-layer polyelectrolyte membrane according to claim 5 , wherein the metal oxide comprises titanium oxide, zirconium oxide, niobium oxide and cerium oxide or a combination thereof.

[0226] 8. The double-layer polyelectrolyte membrane according to claim 5, wherein the metal oxide comprises cerium oxide.

[0227] 9. The double-layer polyelectrolyte membrane according to any one of claims 1 to 8, wherein the metal oxide is doped with one or more dopants.

[0228] 10. The double-layer polyelectrolyte membrane according to claim 9, wherein the metal oxide doped with one or more dopants is selected from gadolinium-doped cerium oxide, samarium-doped cerium oxide, niobium-doped titanium oxide or cerium-doped zirconium oxide.

[0229] 11. The double-layer polyelectrolyte membrane of claim 9, wherein the metal oxide comprises about 0.5 wt% to about 5 wt% of the dopant.

[0230] 12. The double-layer polyelectrolyte membrane of any one of claims 1 to 11, wherein the metal oxide is in the form of crystalline particles having a characteristic size of about 1 nm to about 100 nm.

[0231] 13. The double-layer polyelectrolyte membrane of any one of claims 1 to 11, wherein the metal oxide is in the form of crystalline particles having a characteristic size of about 2 nm to about 50 nm.

[0232] 14. The double-layer polyelectrolyte membrane according to any one of claims 1 to 13, wherein the second layer further comprises a polymer matrix, and the metal oxide is dispersed within the polymer matrix.

[0233] 15. The double-layer polyelectrolyte membrane of claim 14, wherein the second layer comprises from about 5 wt% to about 85 wt% of the metal oxide.

[0234] 16. A double-layer polyelectrolyte membrane according to claim 14 or 15, wherein the polymer matrix comprises one or more first polymers, and the one or more first polymers are selected from polyethers, polysulfonates, polysulfones, polyimidazoles, polysiloxanes, polyacrylates, polysulfides, polyolefins, polyamides, triazoles, benzimidazoles, polyesters and polycarbonates.

[0235] 17. A double-layer polyelectrolyte membrane according to claim 14 or 15, wherein the one or more first polymers are selected from polyethylene glycol (PEG), polyetheretherketone (PEEK), polytetrahydrofuran, polyvinyl butyral, poly(acrylonitrile-butadiene-styrene), polyetherpyridine, polyphenylsulfone (PPS), polyphosphazene (POP), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ether (PPO), polyaryletherketone (PAEK), polysulfone, polysulfide sulfone, polyimide (PI), polyetherimide (PEI), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and polyamine.

[0236] 18. The double-layer polyelectrolyte membrane according to claim 14 or 15, wherein the one or more first polymers are selected from the group consisting of PEG, PEEK, PPS, PBI and PVDF.

[0237] The bilayer polyelectrolyte membrane of claim 16 , wherein the first polymer is PEG.

[0238] 20. The bilayer polyelectrolyte membrane of any one of claims 16-19, wherein the one or more first polymers have a molecular weight of about 250,000 g / mol to about 4,000,000 g / mol.

[0239] 21. The bilayer polyelectrolyte membrane of claim 20, wherein the one or more first polymers have a molecular weight of about 500,000 g / mol to about 1,000,000 g / mol.

[0240] 22. The double-layer polyelectrolyte membrane of any one of claims 16-21, wherein the one or more first polymers are sulfonated.

[0241] 23. The double-layer polyelectrolyte membrane of any one of claims 16-22, wherein at least one of the one or more first polymers is cross-linked.

[0242] 24. The double-layer polyelectrolyte membrane of claim 23, wherein at least one of the one or more first polymers comprises a cross-linking moiety represented by one of the following structural formulas:

[0243]

[0244]

[0245] in:

[0246] R 1 , R 2 , R 3 , R 4 and R5 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-14 Aryl and C 6-14 Aryl (C 1-12 Alkylene);

[0247] R a H or C 1-12 alkyl;

[0248] M 2+ Selected from Mr. 2+ , Ca 2+ , Ba 2+ and Al(X) 2+ , wherein X is a halogen, acetate or nitrate; and

[0249] symbol represents the point of attachment of the crosslinking moiety to the repeating units of the one or more first polymers.

[0250] 25. The double-layer polyelectrolyte membrane according to claim 24, wherein the cross-linking portion is represented by one of the following structural formulas:

[0251]

[0252] 26. The double-layer polyelectrolyte membrane of claim 24, wherein the cross-linked portion is represented by the following structural formula:

[0253] 27. The bilayer polyelectrolyte membrane of any one of claims 1-26, wherein the first layer further comprises a porous matrix comprising a second polymer, and wherein the PFSA polymer and the second polymer form an interpenetrating network.

[0254] 28. The bilayer polyelectrolyte membrane of claim 27, wherein the first layer comprises from about 70 wt% to about 99 wt% of the PFSA polymer.

[0255] 29. A double layer polyelectrolyte membrane according to any of claims 27 or 28, wherein the second polymer is PTFE.

[0256] 30. The double-layer polyelectrolyte membrane of claim 29, wherein the second polymer is expanded PTFE.

[0257] 31. The bilayer polyelectrolyte membrane of any one of claims 23-30, wherein the one or more first polymers have a gel fraction of about 50% to about 100%.

[0258] 32. The double layer polyelectrolyte membrane of any one of claims 1-31, wherein the first layer is about 5 μm to about 175 μm thick.

[0259] 33. The double layer polyelectrolyte membrane of any one of claims 1-32, wherein the second layer is about 0.2 μm to about 170 μm thick.

[0260] 34. The bilayer polyelectrolyte membrane of claim 33, wherein the second layer is about 0.2 μm to about 10 μm thick.

[0261] 35. A double-layer polyelectrolyte membrane according to any one of claims 1-34, wherein the first layer is continuous.

[0262] 36. A double-layer polyelectrolyte membrane according to any one of claims 1-35, wherein the second layer is continuous.

[0263] 37. A double-layer polyelectrolyte membrane according to any one of claims 1 to 36, wherein the membrane is unsupported.

[0264] 38. The double-layer polyelectrolyte membrane of claim 1, wherein:

[0265] The first layer is composed of PFSA, wherein the PFSA is a polymer comprising a repeating unit represented by structural formula (I):

[0266]

[0267] in:

[0268] x is an integer between 5 and 14,

[0269] m is 1 or 2, and

[0270] n is 2 or 3;

[0271] The metal oxide is CeO2, and

[0272] The second layer further comprises a cross-linked PEG comprising a cross-linking moiety represented by the following structural formula:

[0273] 39. A double-layer polyelectrolyte membrane according to any one of claims 1 to 13, wherein:

[0274] The second layer further comprises glass, and

[0275] The metal oxide is dispersed in the glass.

[0276] 40. The double-layer polyelectrolyte membrane of claim 39, wherein the glass comprises niobium oxide, silicon dioxide, tantalum oxide, tungsten oxide, vanadium oxide, or molybdenum oxide.

[0277] 41. A method for manufacturing a double-layer polyelectrolyte membrane according to any one of claims 1 to 38, the method comprising:

[0278] providing a first layer having a first side, and a suspension comprising a metal oxide and a solvent; and

[0279] The first side of the first layer is coated with the suspension, thereby producing a coated first layer.

[0280] 42. The method of claim 41, wherein the suspension comprises from about 1 volume % to about 74 volume % of the metal oxide.

[0281] 43. The method of claim 42, wherein the suspension comprises about 35% by volume of the metal oxide.

[0282] 44. The method of any one of claims 41-43, wherein the suspension further comprises a first polymer.

[0283] 45. The method of claim 44, wherein the suspension comprises from about 0.2 wt% to about 25 wt% of the first polymer.

[0284] 46. ​​The method of claim 45, wherein the suspension comprises about 0.5% by weight of the first polymer.

[0285] 47. The method of any one of claims 44-46, wherein the first polymer comprises a cross-linkable group.

[0286] 48. The method of claim 47, wherein the crosslinkable group is selected from OH, NH2, SH, C(O)OH, C(O)Cl, C(O)Br, NHNH2, N3, S(O)2OH, S(O)2Cl, -NCO,

[0287] 49. The method of claim 48, wherein the crosslinkable group is

[0288] 50. The method of any one of claims 41-49, wherein the suspension further comprises a cross-linking initiator.

[0289] 51. The method of any one of claims 41-50, further comprising the step of crosslinking the first polymer under conditions sufficient for the crosslinking initiator to initiate crosslinking of the first polymer.

[0290] 52. The method of claim 51, wherein the conditions sufficient for the cross-linking initiator to initiate cross-linking of the first polymer comprise visible light irradiation, UV light irradiation, application of heat, microwave irradiation, ultrasound, or gamma ray irradiation.

[0291] 53. The method according to any one of claims 50-52, wherein the cross-linking initiator is selected from 2,2-dimethoxy-2-phenylacetophenone (DMPA), azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO).

[0292] 54. The method of any one of claims 50-53, wherein the suspension comprises from about 0.5 wt% to about 50 wt% of the cross-linking initiator.

[0293] 55. The method of claim 54, wherein the suspension comprises from about 5 wt% to about 15 wt% of the cross-linking initiator.

[0294] 56. The method of any one of claims 41-49, wherein the suspension further comprises a cross-linking agent.

[0295] 57. The method of claim 56, further comprising the step of reacting the first polymer with the cross-linking agent under conditions sufficient to cause a cross-linking reaction between the first polymer and the cross-linking agent.

[0296] 58. The method of claim 57, wherein the conditions sufficient to cause a cross-linking reaction between the first polymer and the cross-linking agent comprise irradiation with visible light, irradiation with UV light, and / or application of heat.

[0297] 59. The method of claim 58, wherein the conditions sufficient to cause a cross-linking reaction between the first polymer and the cross-linking agent include heating the coated first layer to a cross-linking temperature of about 150°C to about 200°C for a cross-linking time of about 2 hours to about 96 hours.

[0298] 60. The method of claim 59, wherein the cross-linking temperature is about 180°C.

[0299] 61. The method of claim 59 or 60, wherein the cross-linking time is about 4 hours.

[0300] 62. The method of any one of claims 56-61, wherein the cross-linking agent is selected from a polyol, an aldehyde, an amine, an epoxide, a thiol, or a compound containing a terminal olefin or an alkyne.

[0301] 63. The method of any one of claims 56-61, wherein the cross-linking agent is selected from glycerol, ethylene glycol, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol, glutaraldehyde, styrene and tetrafluorostyrene.

[0302] 64. The method of claim 63, wherein the cross-linking agent is a polyol.

[0303] 65. The method of claim 63, wherein the cross-linking agent is ethylene glycol or glycerol.

[0304] 66. The method of any one of claims 41-65, wherein coating the first side of the first layer with the suspension comprises spraying, spin coating, drop coating, zone casting, dip coating, knife coating, printing, vacuum filtration, slot die coating, curtain coating, or a combination thereof.

[0305] 67. The method of claim 66, wherein coating the first side of the first layer with the suspension comprises spraying.

[0306] 68. The method of any one of claims 41-67, wherein the solvent is selected from dimethylformamide, tetrahydrofuran, N-methylformamide, formamide, acetonitrile, dimethylacetamide, propylene carbonate, ethylene carbonate, N-methylpyrrolidone, dimethyl sulfoxide, or a combination thereof.

[0307] 69. The method of claim 68, wherein the solvent is dimethylformamide.

[0308] 70. A membrane electrode assembly (MEA), comprising:

[0309] A double-layer polyelectrolyte membrane according to any one of claims 1 to 40;

[0310] cathode; and

[0311] anode,

[0312] The double-layer electrolyte membrane is disposed between the anode and the cathode.

[0313] 71. The MEA of claim 70, wherein the cathode is disposed on the first layer of the double-layer electrolyte membrane, and the anode is disposed on the second layer of the double-layer electrolyte membrane.

[0314] 72. The MEA of claim 70, wherein the anode is disposed on the first layer of the double-layer electrolyte membrane, and the cathode is disposed on the second layer of the double-layer electrolyte membrane.

[0315] 73. A fuel cell comprising one or more MEAs according to any one of claims 70-72 and one or more airflow bipolar plates.

[0316] Example

[0317] Material

[0318] PFSA membrane (NR-211) was purchased from Fuel Cell Store. Sulfuric acid (H2SO4) was purchased from Sigma-Aldrich (95-98%, CAS 7664-93-9). Ethylene glycol was purchased from Sigma-Aldrich (≥99%, CAS107-21-1).

[0319] Example 1. Synthesis of cerium oxide nanocrystals.

[0320] In the synthesis of 4nm cerium oxide nanocrystals, 8.68g of cerium nitrate hexahydrate (20mmol, Sigma 99.999%) and 53.6g of oleylamine (200mmol, 90% Acros Organics) were dissolved in 100ml of 1-octadecene (Aldrich 90%). Doping can be introduced by replacing part of the cerium nitrate with an aliovalent dopant such as gadolinium nitrate or samarium nitrate. After initial mixing, the solution was stirred at 80°C under nitrogen for one hour, and then degassed at 120°C under <100mTorr vacuum for one hour. Then, the solution was heated to 230°C at 10°C / min. Once the solution temperature reached 230°C, the solution was further heated to 250°C and allowed to react for two hours. After the reaction was complete, the solution was cooled in air at about 80°C, and 50mL of toluene was added to the solution. The solution was then centrifuged at 1500rpm for 10 minutes to remove a large amount of precipitate. The supernatant was mixed with 600 mL of reagent alcohol and centrifuged at 7000 rpm for 10 minutes. The nanocrystals were purified three times after synthesis by dispersion and precipitation with a hexane / reagent alcohol combination, filtered using a 0.2 μm PTFE filter and stored.

[0321] Example 2. Nanocrystal ligand exchange.

[0322] The cerium oxide nanocrystals prepared according to Example 1 suspended in hexane (Aldrich>95% n-hexane) were purified by four suspension and precipitation cycles with hexane and reagent alcohol or acetone. The nanocrystal concentration was then diluted to 5 mg / mL, and an equal volume of N,N-dimethylformamide (DMF) (Aldrich≥99%) was added to form a two-phase mixture. The two-phase mixture was agitated to ensure proper washing of the nanocrystals before ligand stripping. If the two-phase mixture became turbid during agitation, the nanocrystals were precipitated and washed twice more, and the test was repeated. If the mixture remained clear and separated back into a two-phase mixture, nitrosyl tetrafluoroborate (Aldrich 95%) in an amount equivalent to half the weight of the nanocrystals in the solution was added to the mixture, and the mixture was sonicated for thirty minutes to promote ligand stripping. After phase transfer from hexane to DMF, the hexane phase was removed, replaced with fresh hexane and shaken. After phase separation, the hexane phase was removed, and this hexane wash was repeated twice more. The nanocrystals were purified by suspending and precipitating them in DMF with a DMF / toluene combination up to six times, tracking the DMF / toluene ratio from 1:2 to 1:3, 1:4 and finally to a DMF to toluene ratio of 1 to 6. For the final wash, the nanocrystals were precipitated with toluene and resuspended in anhydrous DMF for storage.

[0323] Example 3. Preparation of polymer solutions and polymer-metal oxide suspensions.

[0324] To prepare a typical polymer solution, a range of 10 to 50 mg of polymer was weighed out in a 4 mL glass vial and 1 mL of solvent was added to the vial along with a 0.25" stir bar. The solution was then allowed to stir overnight at ambient conditions.

[0325] To prepare the composite solution, the ligand-exfoliated nanocrystals were precipitated from solution using the procedure outlined in the purification step for ligand exfoliation in Example 2. A volume of the polymer solution prepared above was added to the centrifuge tube containing the nanocrystal pellet and the whole was sonicated to facilitate resuspension.

[0326] Example 4. The CeO2-PEG (DA) suspension was sprayed on the 211 layer.

[0327] Using Sonotek ExactaCoat A layer of polyethylene glycol diacrylate (PEG(DA)) and cerium oxide (CeO2) was deposited on the substrate. The spray suspension prepared as described in Example 3 consisted of 0.5 wt% PEG(DA) 700 (50 mg PEG(DA)) and 0.04 vol% CeO2 / DMF (35 vol% CeO2 relative to the combined volume of PEG(DA) and CeO2). The suspension was stirred overnight before use. 2,2-dimethoxy-2-phenylacetophenone (DMPA) (10 wt% relative to PEG(DA)) was added to the suspension prior to material deposition and stirred for 30 minutes. During the deposition process, The film substrate was kept under vacuum. The ExactaCoat parameters used were: power 0.8-1.3 W, nozzle height 40 mm, temperature 80 °C, flow rate 0.25-0.5 mL / min. The deposition parameters can be varied as follows:

[0328] Polyethylene glycol diacrylate molecular weight: PEG (DA) 250–4,000,000

[0329] CeO2 amount: 5 volume % -74 volume %;

[0330] Substrate temperature: 5°C–200°C;

[0331] Nozzle height: 10mm–100mm;

[0332] Flow rate: 0.25 mL / min–4 mL / min;

[0333] Power: 0.8W–5W;

[0334] Amount of crosslinking initiator: 0.5 wt%-50 wt%.

[0335] Example 5. The ZrO2-PEG (DA) suspension was sprayed on the 211 layer.

[0336] Spray coating was performed as described in Example 4. The spray suspension prepared as described in Example 3 consisted of 0.5 wt% PEG(DA) 700 (50 mg PEG(DA)) and 0.04 vol% ZrO2 / ethanol (35 vol% ZrO2 relative to the combined volume of PEG(DA) and ZrO2). The following ExactaCoat parameters were used: power 0.8-1.3 W, nozzle height 40 mm, temperature 60°C, flow rate 0.25-0.5 mL / min.

[0337] Example 6. The MnO2-PEG (DA) suspension was sprayed on the 211 layer.

[0338] Spray coating was performed as described in Example 4. The spray suspension prepared as described in Example 3 consisted of 0.5 wt% PEG(DA) 700 (50 mg PEG(DA)) and 0.04 vol% MnO2 / ethanol (35 vol% MnO2 relative to the combined volume of PEG(DA) and MnO2). The following ExactaCoat parameters were used: power 0.8-1.3 W, nozzle height 40 mm, temperature 60°C, flow rate 0.25-0.5 mL / min.

[0339] Example 7. TiO2-PEG (DA) suspension was sprayed on the 211 layer.

[0340] Spray coating was performed as described in Example 4. The spray suspension prepared as described in Example 3 consisted of 0.5 wt% PEG(DA) 700 (50 mg PEG(DA)) and 0.04 vol% TiO2 / ethanol (35 vol% TiO2 relative to the combined volume of PEG(DA) and TiO2). The following ExactaCoat parameters were used: power 0.8-1.3 W, nozzle height 40 mm, temperature 60°C, flow rate 0.25-0.5 mL / min.

[0341] Example 8. Nb2O3-PEG (DA) suspension was sprayed on the 211 layer.

[0342] Spray coating was performed as described in Example 4. The spray suspension prepared as described in Example 3 consisted of 0.5 wt% PEG(DA) 700 (50 mg PEG(DA)) and 0.04 vol% Nb2O3 / ethanol (35 vol% Nb2O3 relative to the combined volume of PEG(DA) and Nb2O3). The following ExactaCoat parameters were used: power 0.8-1.3 W, nozzle height 40 mm, temperature 60°C, flow rate 0.25-0.5 mL / min.

[0343] Example 9. Cross-linking of metal oxide-PEG (DA) layers.

[0344] According to Examples 4-8, The PEG(DA) / metal oxide composite coating on the surface was crosslinked in the spray drying suspension using 2,2-dimethoxy-2-phenylacetophenone (DMPA) as UV initiator (10 wt%). The crosslinking initiator was added to the suspension before deposition. The film was placed under UV light for 1 hour after deposition. The crosslinking parameters can be varied as follows:

[0345] Cross-linking time: 15 minutes-48 hours;

[0346] Crosslinking temperature: up to 200°C.

[0347] Azobisisobutyronitrile (AIBN) was also used instead of DMPA in the solution preparation with the same results.

[0348] Example 10. The CeO2-polyethyleneimine suspension is sprayed on the 211 layer.

[0349] Using Sonotek ExactaCoat A layer of polyethyleneimine and cerium oxide (CeO2) was deposited on the surface. The spray suspension was prepared according to Example 3 and consisted of 0.5 wt% polyethyleneimine (60,000 MW) and 0.04 vol% CeO2 / DMF (35 vol% CeO2 relative to the combined volume of polyethyleneimine and CeO2). The suspension was stirred overnight before use. Dibromopropane (DBP) (30 wt% relative to polyethyleneimine) was added to the solution before material deposition and used immediately. During the deposition process, The film substrate was kept under vacuum. The ExactaCoat parameters used were: power 0.8-1.3 W, nozzle height 40 mm, temperature 80 °C, flow rate 0.25-0.5 mL / min. The deposition parameters can be varied as follows:

[0350] Polyethyleneimine molecular weight: 250–4,000,000;

[0351] CeO2 amount: 5 volume % -74 volume %;

[0352] Substrate temperature: 5°C–200°C;

[0353] Nozzle height: 10mm–100mm;

[0354] Flow rate: 0.25 mL / min–4 mL / min;

[0355] Power: 0.8W–5W;

[0356] Crosslinking amount: 10 wt%-100 wt%.

[0357] Example 11. Cross-linking of CeO2-polyethyleneimine layer.

[0358] According to Example 10, The polyethyleneimine / CeO2 composite coating on the surface was crosslinked using DBP as a crosslinker (30 wt%) in a spray-dried suspension. The crosslinker was added to the suspension before deposition. After deposition, the film was heated to 200°C in air for 2 hours. The crosslinking parameters can be varied as follows:

[0359] Cross-linking time: 5 minutes to 48 hours;

[0360] Crosslinking temperature: up to 250°C.

[0361] Example 12. The CeO2-PPS suspension is sprayed on the 211 layer.

[0362] Using Sonotek ExactaCoat A layer of polyethyleneimine and cerium oxide (CeO2) was deposited on the surface. The spray suspension was prepared according to Example 3 and consisted of 0.5 wt% PPS (55,000 MW) and 0.04 vol% CeO2 / (1:1 DMSO / DMF) (35 vol% CeO2 relative to the combined volume of polyethyleneimine and CeO2). The suspension was stirred overnight before use. During the deposition process, The film substrate was kept under vacuum. The ExactaCoat parameters used were: power 0.8-1.3 W, nozzle height 40 mm, temperature 80 °C, flow rate 0.25-0.5 mL / min. The deposition parameters can be varied as follows:

[0363] PPS molecular weight: 1000-5,000,000;

[0364] CeO2 amount: 5 volume % -74 volume %;

[0365] Substrate temperature: 5°C–200°C;

[0366] Nozzle height: 10mm–100mm;

[0367] Flow rate: 0.25 mL / min–4 mL / min;

[0368] Power: 0.8W–5W;

[0369] Crosslinking amount: 0.5 wt%-100 wt%;

[0370] DMSO amount: 0.5 volume % - 100 volume %.

[0371] Example 13. Cross-linked CeO2-PPS layer.

[0372] According to Example 12, The PPS / CeO2 composite coating on the substrate was cross-linked using residual DMSO from the spray solvent as a cross-linking agent. After deposition, the film was heated to 200°C in air for 2 hours. The cross-linking parameters can be varied as follows:

[0373] Cross-linking time: 15 minutes-48 hours;

[0374] Crosslinking temperature: up to 250°C.

[0375] Example 14. Preparation of membrane electrode assembly.

[0376] The membrane electrode assembly (MEA) uses a double-layer polyelectrolyte membrane and a 5 cm 2 For MEA fabrication, a 3-inch x 3-inch membrane was placed between two gas diffusion electrodes (GDEs), each with an area of ​​5 cm 2 The GDE had a pre-deposited catalyst layer on one side of the microporous layer and was implemented so that the catalyst layer interfaced with the membrane. A 5 cm 2 A 3" x 3" PTFE gasket for the window was used to surround the gas diffusion electrode to prevent reactant gas leakage. The gasket thickness was adjusted to allow 80% compression of the GDE when the MEA was fastened between two fuel cell end plates.

[0377] Example 15. Testing of double-layer polyelectrolyte membranes in fuel cells.

[0378] Membrane performance in fuel cells was evaluated via H2 permeation measurements, fuel cell polarization curves, and accelerated stress testing.

[0379] H2 permeation measurements. H2 permeation was measured by performing cyclic voltammetry, where the cathode side electrode was scanned between 0.1 V and 0.8 V at a voltage scan rate of 2 mV / s at 80°C and 100% RH, with a H2 flow rate of 0.4 lpm on the anode side and an Ar flow rate of 0.4 lpm on the cathode side, and no back pressure. The fuel cell polarization curves were determined by performing constant voltage measurements: from open circuit potential to 0.3 V and back to open circuit potential at 80°C at different RH values, with an increment of 0.5 V between open circuit potential and 0.7 V, an increment of 1 V between 0.7 V and 0.3 V, a H2 flow rate of 0.2 lpm on the anode side, and an air or O2 flow rate of 0.2 lpm on the cathode side, and a back pressure of 50 kPa. g .

[0380] Electrochemical impedance spectroscopy

[0381] In H2 pump mode, 150 mA / cm 2 and 75mA / cm 2 Excitation amplitude for electrochemical impedance spectroscopy measurements. The measurements were performed at 80°C and 100% RH with a H2 flow of 0.05 lpm on the anode side and an Ar flow of 0.05 lpm on the cathode side, without back pressure.

[0382] Fig.16 The data in the study unexpectedly showed that in the presence of CeO2 nanocrystals / cross-linked PEG (DA) composites In the double-layer membrane of 211, the composite and The layers show no contact resistance between each other, which means that protons encounter no additional resistance when moving between the layers. Contact resistance between heterogeneous materials is frequently observed in conductive systems and constitutes a significant obstacle for layered geometries. Therefore, a bilayer system comprising two materials stacked on top of each other is expected to show a decrease in ionic conductivity due to the interface / contact resistance. To evaluate the contact resistance in bilayer membranes, a 25 μm 211 membrane, a 1 μm thick coating comprising 35 vol% 4 nm CeO2 particles in cross-linked PEG (DA) (75% cross-linked), and a 25 μm coated with a 1 μm thick coating comprising 35 vol% 4 nm CeO2 particles in cross-linked PEG (DA) (75% cross-linked). The area specific resistance (ASR) of a 211-layer bilayer membrane. Unexpectedly, the ASR of the bilayer system is almost equal to the sum of the ASR values ​​of the individual layers, which means that protons do not encounter additional resistance when moving between the layers.

[0383] Accelerated Stress Test (AST)

[0384] The accelerated stress test consisted of an aggressive, intense phase and a periodic hydration phase, each of which lasted up to 4.5 hours and 0.5 hours, respectively. During the aggressive, intense phase, the cell was set to 110°C, with a H2 flow rate of 0.1 lpm on the anode, a O2 flow rate of 0.1 lpm on the cathode, no back pressure, and both gases at 30% RH. During the hydration phase, the cell was set to 80°C, with a H2 flow rate of 0.1 lpm on the anode, a O2 flow rate of 0.1 lpm on the cathode, no back pressure, and both gases at 100% RH. During the accelerated stress test, H2 permeation was measured periodically and wastewater was collected. The results of the tests are presented in Figure 4-6 Shown in.

[0385] Fig.13 The data in the present study show that the composites containing CeO2 nanocrystals / cross-linked PEG (DA) 211 The durability of the double-layer film of 211 is At least twice that of 211 film.

[0386] Example 16. Determination of the degree of cross-linking in complexes containing PEG(DA).

[0387] The degree of crosslinking of the membranes containing PEG(DA) was determined by Fourier transform infrared spectroscopy (FTIR). -1 The IR absorption area at (recorded as integral (C=C)) was used to determine the change in the absorption intensity of the C=C bond. The degree of crosslinking was calculated as follows:

[0388]

[0389] The integral (C=C_polymer) refers to the C=C absorption before UV or thermal crosslinking, while the integral (C=C_crosslink) refers to the C=C absorption after UV or thermal crosslinking.

[0390] Example 17. Conductivity measurements of freestanding membranes.

[0391] The membrane conductivity was measured in a Scribner Bekktech BT-112HT conductivity cell with an Admiral Squidstat potentiostat in 4-point probe geometry. The conductivity was evaluated by current measurements during linear sweep voltammetry from -0.5 V to 0.5 V. The conductivity was then calculated from the current-voltage slope and the sample thickness.

[0392] Example 18. Sulfonation of PPS.

[0393] General Procedure: PPS is sulfonated by reacting the polymer with H2SO4. PPS is dissolved in concentrated H2SO4 at a concentration of 25 mg / mL and stirred at 60-70°C for 10-48 hours. The sulfonated polymer is precipitated by adding the reaction mixture dropwise into H2O at 0°C. The resulting precipitated polymer is centrifuged and separated. The sulfonated PPS (sPPS) is redispersed in H2O at room temperature and washed using dialysis until a neutral pH is recorded. The washed sPPS is dried on a hot plate to provide the final product. The degree of sulfonation of the sPPS can be adjusted by adjusting the reaction time (1-72 hours).

[0394] Example Synthesis: PPS (Radel-5000NT) was sulfonated by reacting the polymer with H2SO4. PPS resin was ground into powder using an industrial grinder. PPS powder (20 g) was dissolved in concentrated H2SO4 at a concentration of 25 mg / mL and stirred at 60°C for 8 hours. The resulting sulfonated polymer was precipitated by adding the reaction mixture dropwise to H2O at 0°C. The resulting precipitated polymer was centrifuged and separated. The sulfonated PPS (sPPS) was redispersed in H2O at room temperature and washed using dialysis until a neutral pH was recorded. The washed sPPS was dried on a hot plate to provide the final product. The reaction yield by mass was measured to be 91%. The titration of the resulting product determined the IEC to be 3.605 meq / g (corresponding to 2.0 sulfonic acids per repeating unit), as measured according to the procedure described in Example 3.

[0395] The sulfonated polymers were measured at a concentration of about 10 wt % in DMSO-d6. 1H NMR was used to confirm the polymer structure and degree of sulfonation. A 500 MHz Bruker Ultrashield 500Plus spectrometer was used to acquire 1 H NMR spectra were processed using SpinWorks 4. A pulse angle of 30° and a pulse delay of 5 s were used. 1 H NMR experiments were performed with 32 scans. 1 H NMR spectrum Fig.10 The number and position of the sulfonic acid groups in the repeating unit were determined using the integration of the peaks as shown in Table 1 below. Fig.10 as shown in .

[0396] Table 1. sPPS 1 H NMR peak integration, 1 H NMR IEC values ​​and IEC values ​​determined by titration.

[0397]

[0398] Peak integration and normalization by setting the peak integration of peak B to value "4" are performed, and this value is the number of protons at the B site of each repeating unit (Table 1). The identity attribution of peak B provides space and electronic protection to the B site based on the presence of sulfone bond and is free from sulfonation. The number of sulfonic acid moieties of each repeating unit is calculated by the ratio of peak integration to peak C. In addition, the IEC value is calculated as follows based on the peak integration value. The value of IEC is related to the material weight of each sulfonic acid moiety. This is referred to as effective weight (EW). Since the prepared sPPS has a single polymer skeleton, the sulfonic acid of each repeating unit is calculated using the ratio of C peak integration (which matches the number of sulfonic acid groups in the structure) to any hydrogen peak, using the following formula:

[0399]

[0400] The number of sulfonic acid moieties per repeating unit was converted to EW according to the following formula:

[0401]

[0402] Among them, MW RU is the molecular weight of the repeating unit (400 g / mol for PPS), is the molecular weight of the sulfonic acid portion (82 g / mol). EW is then converted to IEC as follows:

[0403]

[0404] Based on sPPS 1The IEC numbers obtained for each integrated peak in the H NMR spectrum and the average numbers are in good agreement with the experimental IEC values ​​obtained by titration (see Table 1). This agreement indicates that there are no other significant sulfonation positions on the repeating unit and that sPPS contains two sulfonic acid moieties per repeating unit, which are located on the biphenyl portion of the backbone, such as Fig.10 as shown in .

[0405] The teachings of all patents, published applications, and references cited herein are incorporated by reference in their entirety.

[0406] While the invention has been particularly shown and described with reference to example embodiments thereof, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the scope of the invention as encompassed by the appended claims.

Claims

1. A double-layer polyelectrolyte membrane, comprising: A first layer is disposed on the second layer, wherein: The first layer comprises a perfluorosulfonic acid (PFSA) polymer, and The second layer comprises a crystalline metal oxide.

2. The double-layer polyelectrolyte membrane according to claim 1, wherein the PFSA polymer comprises a repeating unit represented by structural formula (I): in: x is an integer between 1 and 15, m is an integer between 0 and 2, n is an integer between 1 and 5, and symbol Represents the point of attachment to the adjacent repeat unit.

3. The double-layer polyelectrolyte membrane according to claim 2, wherein: x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3.

4. The double-layer polyelectrolyte membrane according to claim 2 or 3, wherein the PFSA polymer comprises about 900 to about 1100 repeating units represented by structural formula (I).

5. The double-layer polyelectrolyte membrane according to any one of claims 1 to 4, wherein the metal oxide comprises a reducible metal oxide.

6. A double-layer polyelectrolyte membrane according to any one of claims 1-5, wherein the metal oxide comprises titanium oxide, zirconium oxide, hafnium oxide, vanadium oxide, niobium, tantalum oxide, chromium oxide, molybdenum oxide, tungsten oxide, manganese oxide, iron oxide, cobalt oxide, nickel oxide, cerium oxide, gadolinium oxide and samarium oxide or a combination thereof. 7 . The double-layer polyelectrolyte membrane according to claim 5 , wherein the metal oxide comprises titanium oxide, zirconium oxide, niobium oxide and cerium oxide or a combination thereof.

8. The double-layer polyelectrolyte membrane according to claim 5, wherein the metal oxide comprises titanium oxide, manganese oxide, niobium oxide and cerium oxide or a combination thereof.

9. The double-layer polyelectrolyte membrane according to claim 5, wherein the metal oxide comprises cerium oxide.

10. The double-layer polyelectrolyte membrane according to claim 5, wherein the metal oxide is cerium oxide.

11. The double-layer polyelectrolyte membrane according to any one of claims 1 to 10, wherein the metal oxide is doped with one or more dopants.

12. The double-layer polyelectrolyte membrane according to claim 11, wherein the metal oxide doped with one or more dopants is selected from gadolinium-doped cerium oxide, samarium-doped cerium oxide, niobium-doped titanium oxide or cerium-doped zirconium oxide.

13. The double-layer polyelectrolyte membrane of claim 11, wherein the metal oxide comprises about 0.5 wt% to about 5 wt% of the dopant.

14. The double-layer polyelectrolyte membrane of any one of claims 1 to 13, wherein the metal oxide is in the form of crystalline particles having a characteristic size of about 1 nm to about 100 nm.

15. The double-layer polyelectrolyte membrane of any one of claims 1 to 13, wherein the metal oxide is in the form of crystalline particles having a characteristic size of about 2 nm to about 50 nm.

16. The double-layer polyelectrolyte membrane of claim 15, wherein the crystalline particles have a characteristic size of about 2 nm to about 10 nm.

17. The double-layer polyelectrolyte membrane of claim 15, wherein the crystalline particles have a characteristic size of about 4 nm.

18. The double-layer polyelectrolyte membrane according to any one of claims 1 to 17, wherein the second layer further comprises a polymer matrix, and the metal oxide is dispersed within the polymer matrix.

19. The double-layer polyelectrolyte membrane of claim 18, wherein the second layer comprises from about 5 wt% to about 85 wt% of the metal oxide.

20. The double-layer polyelectrolyte membrane of claim 18, wherein the second layer comprises about 30 wt% to about 45 wt% of the metal oxide.

21. A double-layer polyelectrolyte membrane according to any one of claims 18-20, wherein the polymer matrix comprises one or more first polymers, and the one or more first polymers are selected from polyethers, polysulfonates, polysulfones, polyimidazoles, polysiloxanes, polyacrylates, polysulfides, polyolefins, polyamides, polytriazoles, benzimidazoles, polyesters and polycarbonates.

22. A double-layer polyelectrolyte membrane according to any one of claims 18-20, wherein the one or more first polymers are selected from polyethylene glycol (PEG), polyetheretherketone (PEEK), polytetrahydrofuran, polyvinyl butyral, poly(acrylonitrile-butadiene-styrene), polyetherpyridine, polyphenylsulfone (PPS), polyphosphazene (POP), polybenzimidazole (PBI), polyethersulfone (PES), polyphenylene ether (PPO), polyaryletherketone (PAEK), polysulfone, polysulfide sulfone, polyimide (PI), polyetherimide (PEI), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF) and polyamine.

23. The double-layer polyelectrolyte membrane according to any one of claims 18-20, wherein the one or more first polymers are selected from the group consisting of PEG, PEEK, PPS, PBI and PVDF.

24. The bilayer polyelectrolyte membrane of any one of claims 18-20, wherein the one or more first polymers are selected from the group consisting of PEG, PPS, poly(ethyleneimine) and PVDF.

25. The bilayer polyelectrolyte membrane of claim 24, wherein the one or more first polymers comprise PEG.

26. The bilayer polyelectrolyte membrane of claim 24, wherein the first polymer is PEG.

27. The bilayer polyelectrolyte membrane of claim 25, wherein the first polymer is PEG-diacrylate (PEG(DA)).

28. The double-layer polyelectrolyte membrane of any one of claims 21-27, wherein the one or more first polymers have a molecular weight of about 250,000 g / mol to about 4,000,000 g / mol.

29. The bilayer polyelectrolyte membrane of claim 28, wherein the one or more first polymers have a molecular weight of about 500,000 g / mol to about 1,000,000 g / mol.

30. The double-layer polyelectrolyte membrane of any one of claims 21-24 and 28-29, wherein the one or more first polymers are sulfonated.

31. The double-layer polyelectrolyte membrane according to claim 22 or 30, wherein the first polymer is sulfonated PPS (sPPS).

32. The double-layer polyelectrolyte membrane of claim 30 or 31, wherein the degree of sulfonation of the first polymer is from about 100% to about 300%.

33. The double-layer polyelectrolyte membrane of claim 32, wherein the degree of sulfonation of the first polymer is about 200%.

34. The bilayer polyelectrolyte membrane of any one of claims 30-33, wherein the first polymer comprises an average of from about 1 to about 3 total sulfonic acid, sulfonate, and sulfonamide groups per repeat unit.

35. The bilayer polyelectrolyte membrane of claim 34, wherein the first polymer comprises an average of about 2 total sulfonic acid, sulfonate, and sulfonamide groups per repeat unit.

36. The double-layer polyelectrolyte membrane of any one of claims 21-35, wherein at least one of the one or more first polymers is cross-linked.

37. The double-layer polyelectrolyte membrane of claim 36, wherein the at least one of the one or more first polymers comprises a cross-linking moiety represented by one of the following structural formulas: 2-6 Alkylene, in: R 1 , R 2 , R 3 , R 4 and R 5 Each of which is independently selected from H, C 1-12 Alkyl, C 1-12 Haloalkyl, C 6-14 Aryl and C 6-14 Aryl (C 1-12 Alkylene); R 6 is H or -SO3H, R a H or C 1-12 alkyl; M 2+ Selected from Mr. 2+ , Ca 2+ , Ba 2+ and Al(X) 2+ , wherein X is a halogen, acetate or nitrate; and symbol represents the point of attachment of the crosslinking moiety to the repeating units of the one or more first polymers.

38. The double-layer polyelectrolyte membrane of claim 37, wherein the cross-linking moiety is represented by one of the following structural formulas:

39. The double-layer polyelectrolyte membrane of claim 37, wherein the cross-linked portion is represented by one of the following structural formulas:

40. The double-layer polyelectrolyte membrane of claim 37, wherein the cross-linking moiety is represented by one of the following structural formulas:

41. The double-layer polyelectrolyte membrane of claim 37, wherein the cross-linked portion is represented by one of the following structural formulas:

42. The double-layer polyelectrolyte membrane of claim 37, wherein the cross-linked portion is represented by the following structural formula:

43. The double-layer polyelectrolyte membrane of claim 37, wherein the cross-linked portion is represented by the following structural formula: or 44. The bilayer polyelectrolyte membrane of any one of claims 1-43, wherein the first polymer has a degree of crosslinking of about 10% to about 95%.

45. The bilayer polyelectrolyte membrane of claim 44, wherein the first polymer has a degree of cross-linking of about 70%.

46. ​​The bilayer polyelectrolyte membrane of claim 44, wherein the first polymer has a degree of crosslinking of about 40%.

47. The bilayer polyelectrolyte membrane of any one of claims 1-46, wherein the first layer further comprises a porous matrix comprising a second polymer, and wherein the PFSA polymer and the second polymer form an interpenetrating network.

48. The bilayer polyelectrolyte membrane of claim 47, wherein the first layer comprises from about 70 wt% to about 99 wt% of the PFSA polymer.

49. A double-layer polyelectrolyte membrane according to any one of claims 47 or 48, wherein the second polymer is PTFE.

50. The bilayer polyelectrolyte membrane of claim 49, wherein the second polymer is expanded PTFE.

51. The bilayer polyelectrolyte membrane of any one of claims 36-50, wherein the one or more first polymers have a gel fraction of about 50% to about 100%.

52. The double layer polyelectrolyte membrane of any one of claims 1-51, wherein the first layer is about 5 μm to about 175 μm thick.

53. The double layer polyelectrolyte membrane of claim 52, wherein the first layer is about 25 μm thick.

54. The double layer polyelectrolyte membrane of any one of claims 1-52, wherein the second layer is about 0.2 μm to about 170 μm thick.

55. The bilayer polyelectrolyte membrane of claim 53, wherein the second layer is about 0.2 μm to about 10 μm thick.

56. The bilayer polyelectrolyte membrane of claim 53, wherein the second layer is about 0.5 μm to about 1 μm thick.

57. The bilayer polyelectrolyte membrane of claim 53, wherein the second layer is about 0.7 μm thick.

58. A double-layer polyelectrolyte membrane according to any one of claims 1-57, wherein the first layer is continuous.

59. A double-layer polyelectrolyte membrane according to any one of claims 1-58, wherein the second layer is continuous.

60. A double-layer polyelectrolyte membrane according to any one of claims 1-59, wherein the membrane is unsupported.

61. The double-layer polyelectrolyte membrane of claim 1, wherein: The first layer is composed of PFSA, wherein the PFSA is a polymer comprising a repeating unit represented by structural formula (I): in: x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; The metal oxide is CeO2, and The second layer further comprises a cross-linked PEG comprising a cross-linking moiety represented by the following structural formula:

62. The double-layer polyelectrolyte membrane of claim 1, wherein: The first layer is composed of PFSA, wherein the PFSA is a polymer comprising a repeating unit represented by structural formula (I): in: x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; The metal oxide is CeO2, and The second layer further comprises a cross-linked PEG (DA) comprising a cross-linking moiety represented by the following structural formula:

63. The double-layer polyelectrolyte membrane of claim 62, wherein: The membrane is unsupported, The crystalline particles of CeO2 have a characteristic size of about 4 nm, and The degree of cross-linking of cross-linked PEG (DA) was about 70%.

64. The double-layer polyelectrolyte membrane of claim 1, wherein: The membrane is unsupported, The PFSA is a polymer comprising repeating units represented by structural formula (I): in x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and further wherein The metal oxide is CeO2, The second layer also comprises a cross-linked sPPS containing a cross-linked portion represented by the following structural formula: The sPPS has a sulfonation degree of about 200%, and The degree of cross-linking of the sPPS is about 40%.

65. The double-layer polyelectrolyte membrane of claim 1, wherein: The membrane is unsupported, The PFSA is a polymer comprising repeating units represented by structural formula (I): in x is an integer between 5 and 14, m is 1 or 2, and n is 2 or 3; and further wherein The metal oxide is CeO2, The second layer further comprises a cross-linked sPPS containing a cross-linked portion represented by one of the following structural formulas: The sPPS has a sulfonation degree of about 200%, and The sPPS has a cross-linking degree of about 25% to about 30%.

66. A double-layer polyelectrolyte membrane according to any one of claims 1 to 17, wherein: The second layer further comprises glass, and The metal oxide is dispersed in the glass.

67. A double-layer polyelectrolyte membrane according to claim 66, wherein the glass comprises niobium oxide, silicon dioxide, tantalum oxide, tungsten oxide, vanadium oxide or molybdenum oxide.

68. A method for manufacturing a double-layer polyelectrolyte membrane according to any one of claims 1 to 65, the method comprising: providing a first layer having a first side, and a suspension comprising a metal oxide and a solvent; and The first side of the first layer is coated with the suspension, thereby producing a coated first layer.

69. The method of claim 68, wherein the suspension comprises from about 0.01% to about 74% by volume of the metal oxide.

70. The method of claim 69, wherein the suspension comprises about 0.4% by volume of the metal oxide.

71. The method of claim 68, wherein the suspension comprises from about 1 volume % to about 74 volume % of the metal oxide.

72. The method of claim 68, wherein the suspension comprises about 35% by volume of the metal oxide.

73. The method of any one of claims 68-73, wherein the suspension further comprises a first polymer.

74. The method of claim 73, wherein the suspension comprises from about 0.2 wt% to about 25 wt% of the first polymer.

75. The method of claim 74, wherein the suspension comprises about 0.5% by weight of the first polymer.

76. The method of any one of claims 73-75, wherein the first polymer comprises a cross-linkable group.

77. The method of claim 76, wherein the crosslinkable group is selected from OH, NH2, NH, SH, C(O)OH, C(O)Cl, C(O)Br, NHNH2, N3, S(O)2OH, S(O)2Cl, -NCO, 78. The method of claim 77, wherein the crosslinkable group is 79. The method of claim 77, wherein the cross-linkable group is S(O)2OH.

80. The method of any one of claims 68-79, wherein the suspension further comprises a cross-linking initiator.

81. The method of claim 80, further comprising the step of crosslinking the first polymer under conditions sufficient for the crosslinking initiator to initiate crosslinking of the first polymer.

82. The method of claim 81, wherein the conditions sufficient for the cross-linking initiator to initiate cross-linking of the first polymer comprise visible light irradiation, UV light irradiation, application of heat, microwave irradiation, ultrasound, or gamma ray irradiation.

83. The method according to any one of claims 80-82, wherein the cross-linking initiator is selected from 2,2-dimethoxy-2-phenylacetophenone (DMPA), azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO).

84. The method of any one of claims 80-83, wherein the suspension comprises from about 0.5 wt% to about 50 wt% of the cross-linking initiator.

85. The method of claim 84, wherein the suspension comprises from about 5 wt% to about 15 wt% of the cross-linking initiator.

86. The method of any one of claims 68-79, wherein the suspension further comprises a cross-linking agent.

87. The method of claim 86, further comprising the step of reacting the first polymer with the cross-linking agent under conditions sufficient to cause a cross-linking reaction between the first polymer and the cross-linking agent.

88. The method of claim 87, wherein the conditions sufficient to cause a cross-linking reaction between the first polymer and the cross-linking agent comprise irradiation with visible light, irradiation with UV light, and / or application of heat.

89. The method of claim 88, wherein the conditions sufficient to cause a cross-linking reaction between the first polymer and the cross-linking agent include heating the coated first layer to a cross-linking temperature of about 150°C to about 200°C for a cross-linking time of about 2 hours to about 96 hours.

90. The method of claim 99, wherein the cross-linking temperature is about 180°C.

91. The method of claim 89 or 90, wherein the cross-linking time is about 4 hours.

92. The method of any one of claims 86-91, wherein the cross-linking agent is selected from a polyol, an aldehyde, an amine, an epoxide, a thiol, or a compound containing a terminal olefin or an alkyne.

93. The method of any one of claims 86-91, wherein the cross-linking agent is selected from glycerol, ethylene glycol, hydroquinone, 2,5-dihydroxybenzenesulfonic acid, 2,5-dihydroxybenzene-1,4-disulfonic acid, biphenyl, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol, and tetrafluorostyrene.

94. The method of claim 93, wherein the cross-linking agent is selected from the group consisting of glycerol, ethylene glycol, tetraglycidylbis(p-aminophenyl)methane, phenylenediamine, 4,4'-thiobisbenzenethiol, glutaraldehyde, styrene, and tetrafluorostyrene.

95. The method of claim 92, wherein the cross-linking agent is a polyol.

96. The method of claim 92, wherein the cross-linking agent is ethylene glycol or glycerol.

97. The method of claim 92, wherein the cross-linking agent is hydroquinone or 2,5-dihydroxybenzenesulfonic acid.

98. The method of any one of claims 68-97, wherein coating the first side of the first layer with the suspension comprises spraying, spin coating, drop coating, zone casting, dip coating, knife coating, printing, vacuum filtration, slot die coating, curtain coating, or a combination thereof.

99. The method of claim 98, wherein coating the first side of the first layer with the suspension comprises spraying.

100. The method of any one of claims 68-99, wherein the solvent is selected from dimethylformamide, tetrahydrofuran, N-methylformamide, formamide, acetonitrile, dimethylacetamide, propylene carbonate, ethylene carbonate, N-methylpyrrolidone, dimethyl sulfoxide, or a combination thereof.

101. The method of claim 100, wherein the solvent is dimethylformamide.

102. A membrane electrode assembly (MEA), comprising: A double-layer polyelectrolyte membrane according to any one of claims 1 to 67; cathode; and anode, The double-layer electrolyte membrane is disposed between the anode and the cathode.

103. The MEA of claim 102, wherein the cathode is disposed on the first layer of the double-layer electrolyte membrane, and the anode is disposed on the second layer of the double-layer electrolyte membrane.

104. The MEA of claim 102, wherein the anode is disposed on the first layer of the double-layer electrolyte membrane, and the cathode is disposed on the second layer of the double-layer electrolyte membrane.

105. A fuel cell comprising one or more MEAs according to any one of claims 102-104 and one or more airflow bipolar plates.